Method for preparing a composite material comprising an elastomer, a filler and a crosslinker - Patent Application 20070123333
Patent Information
- Application Number
- JP2023534621
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-12-09
- Filing Date
- 2021-12-08
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2041-12-08
AI Technical Summary
【0013】 ここに開示されるいずれかの態様または方法または実施態様に関して、該当するならば、本方法は、以下の態様のいずれか1つもしくは2つ以上を更に含むことができる:本方法は、複合材をエージングして、エージングした複合材を形成することを更に含んでいる;複合材が少なくとも20℃の温度で少なくとも5日間に亘ってエージングされた;複合材が少なくとも40℃の温度で少なくとも1日間に亘ってエージングされた;エージングされた複合材から調製された加硫物が、エージングされなかった複合材から調製された加硫物の値の10%以下しか増加しない最大のtanδを有している;エージングされた複合材から調製された加硫物が、エージングされなかった複合材から調製された加硫物の価の10%以下しか増加しないペイン効果を有している。
Smart Images

Figure 0007644239000001 
Figure 0007644239000002 
Figure 0007644239000003
Abstract
Description
[Technical field]
[0001] Disclosed herein is a method for preparing composites by mixing a solid elastomer, a wetting filler, and a crosslinking agent. Also disclosed are composites made by the method and the corresponding vulcanizates derived from those composites. [Background technology]
[0002] In the rubber industry there is a constant demand to develop methods for dispersing fillers into elastomers, and it is particularly desirable to develop methods that can do so with respect to the quality, time, effort and / or cost of filler dispersion.
[0003] Many commercially important products are formed as elastomer composites in which reinforcing fillers are dispersed in either various synthetic elastomers, natural elastomers, or elastomer blends. Carbon black and silica, for example, are widely used to reinforce natural rubber and other elastomers. It is customary to produce masterbatches, which are premixes of reinforcing fillers, elastomers, and various optional additives, such as extender oils. Such masterbatches are then compounded with process and curing additives to produce, upon curing, a number of commercially important products. Such products include, for example, pneumatic and non-pneumatic or solid tires for vehicles, including tread portions including caps and bases, undertreads, inner liners, sidewalls, wire skims, carcasses, and the like. Other products include, for example, engine mounts, conveyor belts, windshield wipers, rubber parts for aerospace and marine equipment, vehicle tread elements, seals, liners, gaskets, wheels, bumpers, anti-vibration systems, and the like. Summary of the Invention [Problem to be solved by the invention]
[0004] Although there are many methods for mixing fillers into solid elastomers, there is a continuing need for new methods to obtain acceptable and enhanced elastomer composite dispersion quality and functionality from elastomer composite masterbatches, which translate into acceptable or enhanced properties in the corresponding vulcanized rubber compounds and rubber articles. [Means for solving the problem]
[0005] One embodiment is a method for preparing a composite material comprising the steps of: (a) charging a mixer with at least a solid elastomer, a wet filler comprising carbon black and a liquid present in an amount of at least 20 weight percent based on the total weight of the wet filler, and a crosslinker; (b) mixing at least a solid elastomer, a wetting filler, and a crosslinker to form a mixture in one or more mixing steps, and removing at least a portion of the liquid from the mixture by evaporation; and (c) discharging from the mixer a composite including the filler dispersed in the elastomer at a loading of at least 20 phr, the composite having a liquid content of 10% by weight or less, based on the total weight of the composite; wherein the crosslinking agent is selected from compounds having at least two functional groups, The first functional group is -N(R 1 )(R 2 ),-N(R 1 )(R 2 )(R 3 ) + A - ,-S-SO 3 M ‘ and structures represented by formula (I) and formula (II), [ka] where A is chloride, bromide, iodide, hydroxyl, nitrate or acetate, X=NH, O or S, Y=H, OR 4 , N.R. 4 R5 , -S n R 4 and n is an integer from 1 to 6, and The second functional group is a thiocarbonyl, a nitrile oxide, a nitrone, a nitrile imine, -S-SO 3 M 2 , -S x -R 6 , -SH, -C(R 6 )=C(R 7 )-C(O)R 8 , -C(R 6 )=C(R 7 )-CO 2 R 8 , -C(R 6 )=C(R 7 )-CO 2 M 2 and R 1 ~R 8 are each independently H and C 1 ~C 8 alkyl; M 1 and M. 2 are each independently H, Na + , K + , Li + , N(R') 4 + where each R' is independently selected from H and C 1 ~C 20 alkyl, and x is an integer selected from 1 to 8.
[0006] Another aspect is a method for preparing a composite material comprising the steps of: (a) charging a first mixer with a wet filler comprising at least a solid elastomer and carbon black and a liquid present in an amount of at least 20% by weight based on the total weight of the wet filler; (b) mixing at least the solid elastomer and the wet filler in one or more mixing steps to form a mixture and removing at least a portion of the liquid from the mixture by evaporation; (c) discharging from the first mixer a mixture comprising a filler dispersed in the elastomer at a loading of at least 20 phr, the mixture having a liquid content that is reduced to an amount less than the liquid content at the start of step (b), and the mixture having a material temperature in the range of 100° C. to 180° C.; (d) mixing the mixture from (c) in a second mixer to obtain a composite; and (d) discharging the composite from the second mixer, the composite having a liquid content of less than 3% by weight, based on the total weight of the composite; Wherein a crosslinking agent is charged into the first mixer, the second mixer, or both the first and second mixers, and the crosslinking agent is selected from a compound having at least two functional groups; wherein the first functional group is -N(R 1 )(R 2 ), -N(R 1 )(R 2 )(R 3 ) + A 、 -S-SO 3 M 1 and the structures represented by formula (I) and formula (II), [ka] where A is chloride, bromide, iodide, hydroxyl, nitrate or acetate, X=NH, O or S, Y=H, OR 4 , N.R. 4 R 5 , -S n R 4 and n is an integer selected from 1 to 6; and The second functional group is a thiocarbonyl, a nitrile oxide, a nitrone, a nitrile imine, -S-SO 3 M 2 , -S x -R 6 , -SH, -C(R 6 )=C(R 7 )-C(O)R 8 , -C(R 6 )=C(R7 )-CO 2 R 8 , -C(R 6 )=C(R 7 )-CO 2 M 2 and R 1 ~R 8 are each independently H and C 1 ~C 8 alkyl; M 1 and M. 2 are each independently H, Na + , K + , Li + , N(R') 4 + where each R' is independently selected from H and C 1 ~C 20 alkyl, and x is an integer selected from 1 to 8.
[0007] Another embodiment is a method of preparing a vulcanizate comprising curing a composite prepared by any of the methods disclosed herein in the presence of at least one curative to form a vulcanizate. Other embodiments are the composites, vulcanizates and articles formed therefrom.
[0008] For any aspect, method, or embodiment disclosed herein, if applicable, the method can further include any one or more of the following aspects: the crosslinker further includes at least one spacer between the first and second functional groups, where the at least one spacer is -(CH 2 ) n -, -(CH 2 ) y C(O)-, -C(R 9 )=C(R 10 )-, -C(O)-, -N(R 9 )-, and -C 6 H 4 - selected from, where R 9 and R 10 are independently H and C 1 ~C8 alkyl, and y is an integer selected from 1 to 10; the crosslinker is selected from thiourea, cystamine, and compounds of formula (1), formula (2), and formula (3); H 2 N-Ar-N(H)-C(O)-C(R 6 )=C(R 7 )-CO 2 M 2 (1) H 2 N-(CH 2 ) n -SSO 3 M 2 (2) M 1 O 3 SS-(CH 2 ) n -S-SO 3 M 2 (3) Here, M 1 and M. 2 are each independently H, Na + , and N(R') 4 + and R 7 are independently H and C 1 ~C 6 alkyl, the crosslinker is selected from the compounds of formula (1), and R 6 and R 7 are each H, and the crosslinker is sodium (2Z)-4-[(4-aminophenyl)amino]-4-oxo-2-butenoate.
[0009] With respect to any aspect, or method, or embodiment disclosed herein, if applicable, the method can further include any one or more of the following aspects: the charging step includes charging the mixer with separate charges of the crosslinker and the wet filler; the charging step includes multiple additions of the solid elastomer, the wet filler, and / or the crosslinker; said mixing step is performed in one mixing step; said mixing step is performed in two or more mixing steps; the mixing in (b) is a second mixing step, where the first mixing step includes mixing at least a portion of the solid elastomer and at least a portion of the wet filler and then charging the mixer with the crosslinker; the charging in (a) includes charging the mixer with a mixture including the crosslinker and the wet filler; the charging in (a) includes charging the mixer with a co-pellet including the crosslinker and the wet filler; in at least one of the mixing steps, the method further includes heating the mixer to a temperature of 65° C. or greater, T z in at least one of the mixing steps, the method includes performing the mixing with one or more rotors of a mixer operated at a tip speed of at least 0.6 m / s for at least 50% of the mixing time; the resulting overall specific energy for mixing is at least 1300 kJ / kg composite.
[0010] For any aspect or method or embodiment disclosed herein, if applicable, the method can further include one or more of the following aspects; the wet filler further comprises at least one material selected from carbonaceous materials, silica, nanocellulose, lignin, clay, nanoclay, metal oxides, metal carbonates, pyrolytic carbon, graphene, graphene oxide, reduced graphene oxide, carbon nanotubes, single-walled carbon nanotubes, multi-walled carbon nanotubes, or combinations thereof, and coated and treated materials thereof; the wet filler further comprises silica; the wet filler comprises a liquid present in an amount ranging from 20% to 80% by weight, based on the total weight of the wet filler; the wet filler is in the form of a powder, paste, pellet, or cake.
[0011] For any aspect or method or embodiment disclosed herein, the method can further include any one or more of the following aspects, if applicable: the solid elastomer is selected from natural rubber, functionalized natural rubber, styrene-butadiene rubber, functionalized styrene-butadiene rubber, polybutadiene rubber, functionalized polybutadiene rubber, polyisoprene rubber, ethylene-propylene rubber, isobutylene based elastomers, polychloroprene rubber, nitrile rubber, hydrogenated nitrile rubber, polysulfide rubber, polyacrylate elastomers, fluoroelastomers, perfluoroelastomers, silicone elastomers, and mixtures thereof; the solid elastomer is selected from natural rubber, functionalized natural rubber, styrene-butadiene rubber, functionalized styrene-butadiene rubber, polybutadiene rubber, functionalized polybutadiene rubber, and mixtures thereof.
[0012] For any aspect or method or embodiment disclosed herein, if applicable, the method can further include any one or more of the following aspects: one or more of the mixing steps is a continuous process; one or more of the mixing steps is a batch process.
[0013] For any aspect or method or embodiment disclosed herein, if applicable, the method can further include any one or more of the following aspects: the method further includes aging the composite to form an aged composite; the composite has been aged at a temperature of at least 20° C. for at least 5 days; the composite has been aged at a temperature of at least 40° C. for at least 1 day; a vulcanizate prepared from the aged composite has a maximum tan δ that is no more than 10% higher than that of a vulcanizate prepared from an unaged composite; a vulcanizate prepared from the aged composite has a Payne effect that is no more than 10% higher than that of a vulcanizate prepared from an unaged composite. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] Disclosed herein, in part, are methods of preparing or forming composites by mixing a solid elastomer with a wet filler. Also disclosed herein, in part, are composites, vulcanizates and articles formed therefrom.
[0015] When mixing fillers with elastomers, the challenge is to ensure a long enough mixing time to ensure adequate filler mixing and dispersion before the elastomer in the mixture experiences high temperatures and decomposes. In typical dry mixing processes, mixing times and temperatures are controlled to avoid such degradation, and it is often not possible to optimize filler mixing and dispersion.
[0016] PCT Publication WO2020 / 247663 describes a mixing process of solid elastomers and wet fillers (e.g., including fillers and liquids) that ensures batch times and temperatures are controlled beyond those achievable with known dry mixing processes, the disclosure of which is incorporated herein by reference. Other advantages can be obtained, such as facilitating filler dispersion and / or promoting rubber-filler interaction and / or improving rubber compound properties compared to conventionally mixed masterbatches as they are compounded and vulcanized. At least one or more properties can be improved, such as the ratio of tensile stress at 300% elongation to stress at 100% elongation (M300 / M100) and tangent delta (tan δ) measured at 60°C. Higher M300 / M100 values are believed to be associated with improved tire wear resistance, and lower tan δ values are believed to be associated with improved energy efficiency of tires.
[0017] Disclosed herein is a method that incorporates the use of a wet filler in the mixing process with a solid elastomer and further mixes in a crosslinking agent. The composite formed by the disclosed method can be considered an uncured mixture of filler and elastomer. The composite formed can be considered a mixture or masterbatch. The composite formed can optionally be an intermediate product that can be used in subsequent rubber compounding and one or more vulcanization processes. The composite prior to compounding and vulcanization can also be subjected to further processes, such as one or more holding steps or further mixing steps, one or more further drying steps, one or more extrusion steps, one or more calendaring steps, one or more grinding steps, one or more granulation steps, one or more baling steps, one or more twin-screw exhaust extrusion steps, or one or more rubber processing steps, to obtain a rubber compound or rubber article.
[0018] In one embodiment, disclosed herein is a method for preparing a composite material, comprising the steps of: (a) charging a mixer with a wet filler comprising at least a solid elastomer, carbon black, and a liquid present in an amount of at least 20% by weight based on the total weight of the wet filler, and a crosslinker; (b) mixing at least a solid elastomer, a wetting filler, and a crosslinker in one or more mixing steps to form a mixture and removing at least a portion of the liquid from the mixture by evaporation; and (c) discharging from the mixer a composite including the filler dispersed in the elastomer at a loading of at least 20 phr, the composite having a liquid content of 10% by weight or less, based on the total weight of the composite; wherein the crosslinking agent is selected from compounds having at least two functional groups, The first functional group is -NR 1 R 2 ,-N(R 1 )(R 2 )(R 3 ) + A - ,-S-SO 3 M 1 and structures represented by formula (I) and formula (II), [ka] where A is chloride, bromide, iodide, hydroxyl, nitrate or acetate, X=NH, O or S, Y=H, OR 4 , N.R. 4 R 5 , -S n R 4 and n is an integer from 1 to 6, and The second functional group is a thiocarbonyl, a nitrile oxide, a nitrone, a nitrile imine, -S-SO 3 M 2 , -S x -R 6 , -SH, -C(R 6 )=C(R7 )-C(O)R 8 , -C(R 6 )=C(R 7 )-CO 2 R 8 , -C(R 6 )=C(R 7 )-CO 2 M 2 and R 1 ~R 8 are each independently H and C 1 ~C 8 alkyl; M 1 and M. 2 are each independently H, Na + , K + , Li + , N(R') 4 + where each R' is independently selected from H and C 1 ~C 20 alkyl, and x is an integer selected from 1 to 8.
[0019] Without wishing to be bound by any theory, it is believed that the mixing process with the wet filler promotes the dispersion of the filler, while the crosslinker interacts with the filler and / or elastomer to generate stronger interactions between the filler and the elastomer. Alternatively, the crosslinker can have at least two functional groups, a first and a second functional group that can interact with the elastomer and / or the filler. The interaction can include adsorption or chemical bonding, such as via ionic interactions, dipole-dipole interactions, hydrogen bonds, covalent bonds, etc. In the composite, the crosslinker can be present in the same form as it is loaded, or in a different form, for example when it interacts with the filler and / or elastomer.
[0020] A crosslinker having at least two functional groups can have two, three, or more than three functional groups. In any of these embodiments, the crosslinker is -NR 1 R2 , -N(R 1 )(R 2 )(R 3 ) + A - , -S-SO 3 M 1 and a first functional group which can be selected from structures represented by formula (I) and formula (II). [ka] where A is chloride, bromide, iodide, hydroxyl, nitrate or acetate; X=NH, O, or S; Y=H, OR 4 , N.R. 4 R 5 , or -S n R 4 and n is an integer selected from 1 to 6. In certain embodiments, the first functional group is -NR 1 R 2 (For example, -NHR 1 or -NH 2 ), -CO 2 M 1 , and -S-SO 3 M 1 can be selected from:
[0021] The crosslinker may further comprise a second functional group, the second functional group being a thiocarbonyl, a nitrile oxide, a nitrone, a nitrile imine, -S-SO 3 M 2 , -S x -R 6 , -SH, -C(R 6 )=C(R 7 )-C(O)R 8 , -C(R 6 )=C(R 7 )-CO 2 R 8 , -C(R 6 )=C(R 7 )-CO 2 M 2 In certain embodiments, the second functional group can be selected from -S-SO 3 M 2 and -CR6 =CR 7 -CO 2 M 2 where the functional group is selected from -CO 2 M 1 , and -S-SO 3 M 1 , -S-SO 3 M 2 , and -CR 6 =CR 7 -CO 2 M 2 which may be selected from acids or salts thereof, e.g. M 1 and M. 2 are independently H, Na + , K + , Li + , and N(R') 4 + (e.g., ammonium salts, where each R' is independently selected from H and C 1 ~C 20 Alkyl, e.g. C 1 ~C 12 Alkyl or C 1 ~C 6 Alkyl or C 1 ~C 4 alkyl, e.g., monoalkyl, dialkyl, trialkyl, or tetraalkyl ammonium salts), where the crosslinker is selected from two or more M 1 Or two or more M 2 Each M 1 or M 2 are independently H, Na + , K + , Li + , and N(R') 4 + can be selected from:
[0022] In the embodiments described herein, R 1 ~R 8 are independently H and C 1 ~C 8 alkyl; M 1 and M.2 are each independently H, Na + , K + , Li + , N(R') 4 + and x is an integer selected from 1 to 8.
[0023] Alternatively, the first functional group can interact with the carbon black. The carbon black can have one or more types of surface functional groups, such as, but not limited to, oxygen-containing groups, such as carboxylic acids (and their salts), hydroxyls (e.g., phenols), esters or lactones, ketones, aldehydes, anhydrides, and benzoquinones. Alternatively, the second functional group can interact with a solid elastomer. The solid elastomer can be a natural elastomer, a synthetic elastomer, and mixtures thereof. For example, the solid elastomer can be selected from natural rubber, functionalized natural rubber, styrene-butadiene rubber, functionalized styrene-butadiene rubber, polybutadiene rubber, functionalized polybutadiene rubber, polyisoprene rubber, ethylene-propylene rubber, isobutylene-based elastomers, polychloroprene rubber, nitrile rubber, hydrogenated nitrile rubber, polysulfide rubber, polyacrylate elastomers, fluoroelastomers, perfluoroelastomers, silicone elastomers, and mixtures thereof. Alternatively, the solid elastomer can be selected from natural rubber, styrene-butadiene rubber, and polybutadiene rubber. The solid elastomer can have olefinic groups and / or be functionalized with a number of groups.
[0024] Optionally, the first functional group is -NR 1 R 2 (For example, -NH 2 ) and -S-SO 3 M 1 and the second functional group can be selected from -S-SO 3 M 2 and -CR 3 =CR4 -CO 2 M 2 can be selected from:
[0025] The crosslinker can have more than two functional groups. In such a crosslinker, each functional group, e.g., the third, fourth, etc. functional group, can be selected from the list of first and second functional groups disclosed herein. Alternatively, two or more crosslinkers can be used to prepare the composite.
[0026] The crosslinker can further comprise at least one spacer between the first and second functional groups. For example, one or more spacers can be bonded to each other and ultimately to the first and second functional groups. Optionally, at least one spacer can be -(CH 2 ) n -, -(CH 2 ) y C(O)-, -C(R 9 )=C(R 10 )-, -C(O)-, -N(R 9 )-, -C 6 H 4 -, where y is an integer selected from 1 to 10, and R 9 and R 10 are independently H and C 1 ~C 6 is selected from alkyl.
[0027] Exemplary crosslinkers are selected from compounds of formula (1), formula (2) and formula (3). H 2 N-Ar-N(H)-C(O)-C(R 6 )=C(R 7 )-CO 2 M 2 (1) H 2 N-(CH 2 ) n -SSO 3 M 2 (2) M 1 O 3 SS-(CH2 ) n -S-SO 3 M 2 (3) M 1 and M. 2 is defined here, and R 6 and R 7 are independently H and C 1 ~C 8 alkyl (e.g., independently selected from H and C 1 ~C 6 alkyl, or H and C 1 ~C 4 Optionally, M 1 and M. 2 are independently H, Na + , and N(R') 4 + , e.g. H and Na + and R 6 and R 7 are the same, e.g. R 6 and R 7 are each selected from H. An example of a crosslinker of formula (1) is sodium (2Z)-4-4-[(4-aminophenyl)amino]-4-oxo-2-butenoate (commercially available as Sumilink® 200 crosslinker), and an example of a crosslinker of formula (2) is S-(3-aminopropyl)thiosulfate (commercially available as Sumilink® 100 crosslinker (Sumitomo)). An example of a crosslinker of formula (3) is commercially available as Duralink® HTS tire additive (Eastman Chemical Co.). Other crosslinkers include cystamine and thiourea.
[0028] One embodiment is a method for preparing a composite material, comprising the steps of: (a) charging a mixer with at least a solid elastomer, a wet filler comprising carbon black and a liquid present in an amount of 20% by weight or more based on the total weight of the wet filler, and a crosslinker; (b) mixing at least a solid elastomer, a wetting filler, and a crosslinker in one or more mixing steps to form a mixture and removing at least a portion of the liquid from the mixture by evaporation; and (c) discharging from the mixer a composite including the filler dispersed in the elastomer at a loading of at least 20 phr, the composite having a liquid content of 10% by weight or less, based on the total weight of the composite; Here, the crosslinking agent is selected from the following (i) to (viii). (i) dihydrazides disclosed in US Patent Publication No. 2012 / 0277359, the disclosure of which is hereby incorporated by reference, in particular phthalic acid dihydrazide, isophthalic acid dihydrazide, terephthalic acid dihydrazide, succinic acid dihydrazide, adipic acid dihydrazide, azelaic acid dihydrazide, sebacic acid dihydrazide, and isophthalic acid dihydrazide, as disclosed in EP Patent Publication No. 0478274, the disclosure of which is hereby incorporated by reference; and / or (ii) hydrazide compounds as disclosed in U.S. Patent Application Publication No. 2019 / 0177513, the disclosure of which is incorporated herein by reference; and / or (iii) tetrazine compounds as disclosed in U.S. Patent Application Publication No. 2020 / 0231782, the disclosure of which is incorporated herein by reference; and / or (iv) the pyrazolone compounds disclosed in PCT Publication WO2020 / 045575, the disclosure of which is incorporated herein by reference (e.g., Compound 1 and Compound 2); and / or (v) For example, 2,2'-bis(benzimidazolyl-2)ethyl disulfide, as disclosed in U.S. Pat. No. 9,200,145, the disclosure of which is incorporated herein by reference; and / or (vi) For example, N,N'-bis(2-nitropropyl-1,3-diaminobenzene), as disclosed in U.S. Pat. No. 5,213,025, the disclosure of which is incorporated herein by reference; and / or (vii) compounds having a nitroxide radical, such as TEMPO (2,2,6,6-tetramethyl-1-piperidinyloxy radical), as disclosed in U.S. Pat. Nos. 6,084,015, 6,194,509, 8,584,725 and U.S. Patent Publication No. 2009 / 0292044, the disclosures of which are incorporated herein by reference; and / or (viii) 1,3-bis(citraconimidomethyl)benzene, commercially available as Perkalink® 900 anti-reversion agent (RheinChemie Additives, Germany).
[0029] The amount of crosslinking agent charged in the mixer is 10 phr or less, for example, 6 phr or less, 5 hr or less, 4 phr or less, 3 phr or less, or 2 phr or less, for example, 0.1 phr to 10 phr, 0.1 phr to 8 phr, 0.1 phr to 6 phr, 0.1 phr to 5 phr, 0.1 phr to 4 phr, 0.1 phr to 3 phr, 0.2 phr to 10 phr, 0.2 phr to 8 phr, 0.2 phr to 6 phr, 0.2 phr to 5 phr r, 0.2phr to 4phr, 0.2phr to 4phr, 0.2phr to 3phr, 0.5phr to 10phr, 0.5phr to 8phr, 0.5phr to 6phr, 0.5phr to 5phr, 0.5phr to 4phr, 0.5phr to 3phr, 1phr to 10phr, 1phr to 8phr, 1phr to 6phr, 1phr to 5phr, 1phr to 4phr, or 1phr to 3phr.
[0030] The method of preparing the composite comprises the steps of filling or introducing into a mixer at least a solid elastomer, a wetting filler, and a crosslinker, e.g., a) one or more solid elastomers and b) one or more wetting fillers, where at least one filler or at least a portion of the filler is wetted with a liquid while being mixed with the solid elastomer (wetting filler). The solid elastomer is mixed with the wetting filler and the crosslinker to form a mixture during the mixing step. The method includes a mixing step in which at least a portion of the liquid is removed by evaporation, or an evaporation process that occurs during mixing, in one or more mixing steps. The liquid of the wetting filler can be removed by evaporation (and at least a portion can be removed under the claimed mixing conditions) and can be a volatile liquid, e.g., volatile at the bulk mixture temperature. For example, a volatile liquid can be distinguished from an oil (e.g., extender oil, process oil) that can be present during at least a portion of the mixing process, such that the oil is present in the discharged composite, and therefore does not evaporate during a substantial portion of the mixing time.
[0031] The fillers charged into the mixer comprise wet fillers. In their dry state, the fillers may contain no liquid adsorbed on their surface or may contain small amounts of liquid (e.g., water or moisture). For example, carbon black may contain 0% by weight, or 0.1% to 1% by weight, or 3% or less, or 4% or less, and precipitated silica may have a liquid (e.g., water or moisture) content of 4% to 7% by weight, such as 4% to 6% by weight. Such fillers are referred to herein as dry or non-wetting fillers. In the wet fillers of the present invention, liquid or further liquids may be added to the filler and are present on a substantial part or substantially all of the surface of the filler, which may include internal surfaces or pores that the liquid can reach. Thus, sufficient liquid is provided to wet a substantial part or substantially all of the surface of the filler prior to the mixing step with the solid elastomer. During the mixing process, as the wet filler is dispersed into the solid elastomer, at least a portion of the liquid may also be removed and the surface of the filler may then become available for interaction with the solid elastomer.The wet filler may comprise at least 20% by weight, based on the total weight of the wet filler, for example, at least 25% by weight, at least 30% by weight, at least 40% by weight, at least 50% by weight, or from 20% to 99% by weight, 20% to 95% by weight, 20% to 90% by weight, 20% to 80% by weight, 20% to 70% by weight, 20% to 60% by weight, 30% to 99% by weight, 30% to 95% by weight, 30% to 90% by weight, 30% to 80% by weight, 30% to 70% by weight, 30% to 60% by weight, The liquid content of the filler may be expressed as a percentage by mass: 40% to 99% by mass, 40% to 95% by mass, 40% to 90% by mass, 40% to 80% by mass, 40% to 70% by mass, 40% to 60% by mass, 45% to 99% by mass, 45% to 95% by mass, 45% to 90% by mass, 45% to 80% by mass, 45% to 70% by mass, 45% to 60% by mass, 50% to 99% by mass, 50% to 95% by mass, 50% to 90% by mass, 50% to 80% by mass, 50% to 70% by mass, or 50% to 60% by mass. The liquid content of the filler may be expressed as a percentage by mass: 100 x [mass of liquid] / [mass of liquid + amount of dry filler]. Alternatively, the amount of liquid can be determined based on the oil adsorption number (OAN) of the filler, where OAN is determined based on ASTM D2414. OAN is a measure of the structure of the filler and can be used to determine the amount of liquid to wet the filler. For example, a wet filler, such as wet carbon black, wet silica (e.g., precipitated silica), or wet silicon-treated carbon black, can have a liquid content determined according to the formula: k×OAN / (100+OAN)×100. In one embodiment, k is in the range of 0.3 to 1.1, or 0.5 to 1.05, or 0.6 to 1.1, or 0.7 to 1.1, or 0.8 to 1.1, or 0.9 to 1.1, or 0.6 to 1.0, or 0.7 to 1.0, or 0.8 to 1.0, or 0.8 to 1.05, or 0.9 to 1.0, or 0.95 to 1, or 0.95 to 1.1, or 1.0 to 1.1.As an option, the wet filler has a liquid content in the range of 20% to 80%, 30% to 70%, 30% to 60%, 40% to 70%, or 40% to 60%.
[0032] As an alternative, the wet filler has a solid consistency. As an alternative, the dry filler is wetted only to such an extent that the resulting wet filler maintains the form or similar consistency of a powder, particulate, pellet, cake, or paste, and / or has the appearance of a powder, particulate, pellet, cake, or paste. The wet filler does not flow like a liquid (at zero applied stress). As an alternative, the wet filler, when molded into a shape, can maintain its shape at 25°C, even if it is an individual particle, aggregate, pellet, cake, or paste. The wet filler is not a composite made by a liquid masterbatch process and is not any other premixed filler of filler dispersed in a solid elastomer, where the elastomer is the continuous phase. The wet filler is not a slurry of filler and does not have the consistency of a liquid or slurry.
[0033] The liquid used to wet the filler can be or include an aqueous liquid, such as, but not limited to, water. The liquid can include at least one other component, such as, but not limited to, a base, an acid, a salt, a solvent, a surfactant, a crosslinking agent (e.g., when the filler further includes silica), and / or a processing aid and / or any combination thereof. More specific examples of the components include NaOH, KOH, acetic acid, formic acid, citric acid, phosphoric acid, sulfuric acid, or any combination thereof. For example, the base can be selected from NaOH, KOH, and mixtures thereof, or the acid can be selected from acetic acid, formic acid, citric acid, phosphoric acid, or sulfuric acid, and combinations thereof. The liquid can be or include a solvent that is immiscible with the elastomer used (e.g., an alcohol, such as ethanol). Alternatively, the liquid can consist of about 80% to 100% by weight, or 90% to 99% by weight, of water, based on the total weight of the liquid.
[0034] In the methods disclosed herein, at least the solid elastomer, the wet filler, and the crosslinker are loaded (e.g., fed, introduced) into the mixer. The loading step of the solid elastomer and / or the filler and / or the crosslinker can be done in one or multiple steps or additions. Loading can occur in any manner, including but not limited to conveying, metering, dropping, and / or feeding the solid elastomer and the wet filler into the mixer in a batch, semi-batch, or continuous flow. The solid elastomer and the wet filler are not introduced into the mixer as a premix prepared by other means than mixing the solid elastomer and the wet filler. The solid elastomer and the wet filler can be added together, but not as a mixture prepared by other means than mixing the solid elastomer and the wet filler (e.g., the wet filler is not predispersed in the elastomer by other means than mixing the elastomer and the wet filler, where the elastomer is the continuous phase). The mixture, premix or premix of the solid elastomer, wet filler and crosslinker can be charged into the mixer and prepared in any number of known ways, such as in a mixer or vessel.
[0035] The charging of the solid elastomer, the wet filler, and the crosslinker can occur all at once or sequentially, and can occur in any order. The charging can include separate charges of the crosslinker and the wet filler. Alternatively, the charging can include a mixture including the wet filler and the crosslinker. For example, (a) all of the solid elastomer is added first, (b) all of the filler is added first, (c) all of the solid elastomer is added with the wet filler and a portion of the crosslinker, followed by one or more remaining portions of the wet filler and the crosslinker, (d) a portion of the solid elastomer is added and then a portion of the wet filler and / or a portion of the crosslinker is added, (e) at least a portion of the wet filler is added first, and then at least a portion of the solid elastomer and / or at least a portion of the crosslinker is added, (f) simultaneously, or nearly simultaneously, a portion of the solid elastomer, a portion of the wet filler, and a portion of the crosslinker are added as separate charges to the mixer. (g) adding at least a portion of the solid elastomer, at least a portion of the wet filler, and at least a portion of the crosslinker in any order and in one or more portions, mixing at least a portion of the solid elastomer and at least a portion of the wet filler, charging at least a portion of the crosslinker to the mixer, and mixing the solid elastomer, the wet filler, and the crosslinker to form a mixture. Other applicable methods of charging the solid elastomer and the wet filler to the mixer are disclosed in PCT Publication WO2020 / 247663, the disclosure of which is incorporated herein by reference.
[0036] For mixtures containing wet filler and crosslinker, the mixture can be a particulate mixture of wet filler and crosslinker, e.g., a powder. If the crosslinker is a liquid, it can be coated on the wet filler by any method known in the art or mixed in other ways, e.g., dipping, spraying, etc. If the crosslinker is a solid, it can be coated or mixed into the wet filler by a solution or dispersion, e.g., an aqueous solution or dispersion. The powder can be charged as is into the mixer or formed into pellets, i.e., pellets that are a mixture that includes the crosslinker. Alternatively, the solution or dispersion that includes the crosslinker can be mixed with the fluffy carbon black (and, optionally, silica and / or other filler types). In addition to mixing, the solution can also wet the carbon black (and, optionally, silica and / or other filler types) to form a wet filler. The resulting wet filler (e.g., being or including wet carbon black) can then be fed into a pin pelletizer and pelletized by the methods disclosed herein.
[0037] The wet filler disclosed herein comprises carbon black. On a dry basis, the filler comprises, for example, at least 50% by weight of carbon black, at least 60% by weight, at least 70% by weight, at least 80% by weight, at least 90% by weight, at least 95% by weight, at least 99% by weight of carbon black, or substantially all of the filler is carbon black, based on the total weight of the filler. In addition to carbon black, the filler can comprise other filler types, i.e., at least one additional filler. The additional filler can be particulate or fibrous or pasty. For example, particulate fillers are made of separate solids. Such fillers can often have an aspect ratio (e.g., length to diameter) of 3:1 or less, or 2:1 or less, or 1:5 or less. Fibrous fillers can have an aspect ratio of, for example, 2:1 or more, or 3:1 or more, or 4:1 or more, or more.
[0038] As an option, the at least one additional filler is selected from carbonaceous materials, carbon black, silica, nanocellulose, lignin, clay, nanoclay, metal oxides, metal carbonates, pyrolytic carbon, regenerated carbon, recovered carbon black (e.g., rCB, as defined in ASTM D8178-19), graphene, graphene oxide, reduced graphene oxide (e.g., reduced graphene oxide worms as disclosed in PCT Publication No. WO 2019 / 070514 A1, the disclosures of which are incorporated herein by reference), or densified reduced graphene oxide granules (U.S. Provisional Patent Application No. 62 / 857,296, filed June 5, 2019, and PCT Publication No. 2020 / 247681, the disclosures of which are incorporated herein by reference), carbon nanotubes, single-walled carbon nanotubes, multi-walled carbon nanotubes, or combinations thereof, or corresponding coated materials (e.g., silicon-treated carbon black) or chemically treated materials thereof (e.g., chemically treated carbon black). Other suitable fillers include carbon nanostructures (CNS, single CNS), multiple carbon nanotubes (CNTs) that are branched, e.g., dendrimer-like, interdigitated, entangled, and / or crosslinked into a polymeric structure sharing a common wall with each other. CNS fillers are described in U.S. Pat. No. 9,447,259 and PCT Application PCT / US2021 / 027814, the disclosures of which are incorporated herein by reference. Mixtures of additional fillers can also be used, such as silica and carbon black, silica and silicon-treated carbon black, and carbon black and silicon-treated carbon black. The filler can be chemically treated (e.g., chemically treated carbon black, chemically treated silica, silicon-treated carbon black) and / or chemically modified. The filler can be or include carbon black with attached organic groups. The filler can have one or more coatings present on the filler (e.g., silicon-coated material, silica-coated material, carbon-coated material).The fillers may be oxidized and / or have other surface treatments. There is no restriction as to the type of filler that can be used (e.g., silica, carbon black, or other fillers).
[0039] Additional fillers can include fibrous fillers, such as natural, semi-synthetic, and / or synthetic fibers (e.g., nano-sized carbon filaments), such as the short chain fibers disclosed in PCT Publication WO2021 / 153643, the disclosure of which is incorporated herein by reference. Other fibrous fillers include poly(p-phenylene terephthalamide), commercially available as Kevlar® pulp (Du Pont).
[0040] Other suitable fillers include bio-derived or bio-based materials (derived from biological sources, recycled materials, or other renewable or sustainable fillers include hydrothermal carbon (HTC, where the filler comprises lignin processed by hydrothermal carbonization as described in U.S. Pat. Nos. 10,035,957 and 10,428,218, the disclosures of which are incorporated herein by reference), rice husk silica, carbon from methane pyrolysis, modified polysaccharide particles, starch, siliceous earth, crumb rubber, and functionalized crumb rubber. Exemplary modified polysaccharide particles include those described in U.S. Patent Application Publication Nos. 2020 / 0181370 and 2020 / 0181370. and those described in US Pat. No. 2020 / 0190270, the disclosures of which are incorporated herein by reference. For example, the polysaccharide can be selected from poly alpha-1,3-glucan, poly alpha-1,3-1,6-glucan, water-insoluble alpha-(1,3-glucan) polymers having 90% or more alpha-1,3-glycosidic bonds, less than 1% by weight of alpha-1,3,6-glycosidic branch points, and a number-average degree of polymerization ranging from 55 to 10,000, dextran, a composition comprising a poly alpha-1,3-glucan ester compound, and a water-insoluble cellulose having a weight-average degree of polymerization (DPw) of about 10 to 1000 and a cellulose II crystal structure.
[0041] As one option, the filler of the wet filler can be or can include a mixture of carbon black and at least one additional filler (e.g., silica, silicon treated carbon black, etc.) in any weight ratio so long as at least 50% by weight (or at least 60% by weight, at least 70% by weight, at least 80% by weight, at least 90% by weight, at least 95% by weight, at least 99% by weight) of the filler is carbon black on a dry basis. The wetting filler can have liquid present in an amount of 25% to 75% by weight, e.g., 30% to 75%, 40% to 75%, 45% to 75%, 50% to 75%, 30% to 70%, 40% to 70%, 45% to 70%, 50% to 70%, 30% to 65%, 40% to 65%, 45% to 65%, 50% to 65%, 30% to 60%, 40% to 60%, 45% to 60%, or 50% to 60% by weight, based on the total weight of the wetting filler. At least one additional filler can be wetted such that the mixture of fillers has a liquid content of at least 20% by weight, based on the total weight of the wetting filler, or any amount disclosed herein.
[0042] In addition to the wetting filler, as an option, the mixture can further include one or more non-wetting fillers (e.g., any filler that is not wetted as described herein, e.g., a dry filler, e.g., a filler having 10% or less liquid by weight). When non-wetting fillers are present, the total amount of filler is such that at least 50%, or at least 60%, at least 70%, at least 80%, at least 90%, at least 95% by weight of the total amount of filler is wet filler, e.g., 50%-99%, 60%-99%, 70%-99%, 80%-99%, 90%-99%, or 95%-99% of the total amount of filler is wet filler, with the remainder of the filler being in a non-wetting state or not considered to be wet filler.
[0043] The amount of filler (e.g., filler alone or wet filler with other fillers) loaded into the mixture is at least 20 phr, at least 30 phr, at least 40 phr, or from 20 phr to 250 phr, from 20 phr to 200 phr, from 20 phr to 180 phr, from 20 phr to 150 phr, from 20 phr to 100 phr, from 20 phr to 90 phr, from 20 phr to 80 phr, from 30 phr to 200 phr, from 30 phr to 180 phr, from 30 phr to 150 phr, from 20 phr to 90 phr, from 20 phr to 80 phr, from 30 phr to 20 ... The phr range may be targeted to be 150 phr, 30 phr to 100 phr, 30 phr to 80 phr, 30 phr to 70 phr, 40 phr to 200 phr, 40 phr to 180 phr, 40 phr to 150 phr, 40 phr to 100 phr, 40 phr to 80 phr, 35 phr to 65 phr, or 30 phr to 55 phr, or other amounts within or outside one or more of these ranges (on a dry weight basis). The above phr amounts may also apply to fillers dispersed in the elastomer (filler loading). Other filler types, mixtures, combinations, etc. may also be used, such as those disclosed in PCT Publication WO2020 / 247663, the disclosure of which is incorporated herein by reference.
[0044] For the solid elastomers used and mixed with the wet filler, the solid elastomer can be a dry elastomer or a substantially dry elastomer. The solid elastomer can have a liquid content (e.g., solvent or water content) of 5% or less by weight, for example 4% or less by weight, 3% or less by weight, or 2% or less by weight, 1% or less by weight, or 0.1% to 5% by weight, 0.5% to 5% by weight, 1% to 5% by weight, 0.5% to 4% by weight, etc., based on the total weight of the solid elastomer. The solid elastomer (e.g., the starting solid elastomer) can be completely elastomeric (including a starting liquid, e.g., water, content of 5% or less by weight) or can be an elastomer that also includes one or more fillers and / or other ingredients. For example, a solid elastomer can be 50% to 99.9% by weight elastomer having 0.1% to 50% by weight filler predispersed in the elastomer, where the predispersed filler is added to the wet filler. Such elastomers can be prepared by a dry blending process between unwetted filler and solid elastomer. Alternatively, a composite made by blending wet filler and solid elastomer (by the processes disclosed herein) can be used as the solid elastomer and further blended with wet filler by the processes disclosed herein. However, a solid elastomer is not a composite, mixture or compound made by a liquid masterbatch process, nor is it any other preblended composite of filler dispersed in elastomer while the elastomer is in a liquid state, such as a latex, suspension or solution.
[0045] Any solid elastomer can be used in the present method. Exemplary elastomers include natural rubber (NR), functionalized natural rubber, synthetic elastomers such as styrene-butadiene rubber (SBR, e.g., solution SBR (SSBR), emulsion SBR (ESBR), or oil-extended SSBR (OESSB+R)), functionalized styrene-butadiene rubber, polybutadiene rubber (BR), functionalized polybutadiene rubber, polyisoprene rubber (IR), ethylene-propylene rubber (EPDM), isobutylene-based elastomers (e.g., butyl rubber), halogenated butyl rubber, polychloroprene rubber (CR), nitrile rubber (NBR), hydrogenated nitrile rubber (HNBR), fluoroelastomers, perfluoroelastomers, and silicone rubbers, such as natural rubber, and blends thereof, such as natural rubber, styrene-butadiene rubber, polybutadiene rubber, and mixtures thereof, such as a mixture of a first and a second solid elastomer. Other synthetic polymers that can be used in the present method (either alone or in mixtures) include hydrogenated SBR, and thermoplastic block copolymers (e.g., recyclable, etc.). Synthetic polymers include copolymers of ethylene, propylene, styrene, butadiene, and isoprene. Other synthetic elastomers include those synthesized by metallocene chemistry, where the metal is selected from Ce, Pr, Nd, Sm, Gd, Tb, Dy, Ho, Tm, Yb, Lu, Co, Ni, and Ti. Polymers made from bio-based monomers can also be used, such as monomers containing modern carbon as defined by ASTM D6866, such as bio-based styrene monomers disclosed in U.S. Pat. No. 9,868,853, the disclosure of which is incorporated herein by reference, or polymers made from bio-based monomers such as butadiene, isoprene, ethylene, propylene, farnesene, and comonomers thereof.When two or more elastomers are used, the two or more elastomers can be charged simultaneously into the mixer as a mixture (in one charge or in two or more charges), or the elastomers can be added separately in any order and amount. For example, the solid elastomer can include natural rubber mixed with one or more elastomers disclosed herein, such as butadiene rubber and / or styrene-butadiene rubber, or SBR mixed with BR, etc. For example, the additional solid elastomer can be added separately to the mixer, and the natural rubber can be added separately to the mixer.
[0046] The solid elastomer can be or include natural rubber, and when the solid elastomer is a mixture, it can include at least 50%, or at least 70%, or at least 90% by weight of natural rubber. The mixture can further include one or more synthetic elastomers, such as styrene-butadiene rubber, functionalized styrene-butadiene rubber, and polybutadiene rubber, and / or any other elastomer disclosed herein.
[0047] Natural rubber can also be chemically modified in any manner. For example, natural rubber can be treated to chemically or enzymatically modify or alter various non-rubber components, or the rubber molecule itself can be modified with various monomers or other chemical groups, such as chlorine. Other examples include epoxidized natural rubber having a nitrogen content of up to 0.3% by weight, as described in PCT Publication WO2017 / 207912.
[0048] Other exemplary elastomers include, but are not limited to, polymers (e.g., homopolymers, copolymers and / or terpolymers) of rubber, 1,3-butadiene, styrene, isoprene, isobutylene, 2,3-dialkyl-1,3-butadienes (wherein the alkyl can be methyl, ethyl, propyl, etc.), acrylonitrile, ethylene, propylene, and the like.
[0049] Other applicable solid elastomers that can be used in the methods disclosed herein are disclosed in PCT Publication WO2020 / 247663, the contents of which are incorporated herein by reference.
[0050] With respect to the mixer that can be used in any of the methods disclosed herein, any suitable mixer capable of mixing (e.g., mixing or compounding) the filler with the solid elastomer can be used. The mixer can be a batch mixer or a continuous mixer. A combination of mixers and processes can be used in any of the methods disclosed herein, and the mixer can be used sequentially, in-line, and / or in combination with other process equipment. The mixer can be an internal mixer, a closed mixer, an open mixer, or an extruder, or a continuous compounder, a kneading mixer, or a combination thereof. The mixer can mix the filler and crosslinker into the solid elastomer and / or can disperse the filler and crosslinker into the elastomer and / or can distribute the filler and crosslinker into the elastomer.
[0051] The mixer can have one or more rotors (at least one rotor). The at least one rotor or the one or more rotors can be a screw-type rotor, an intermeshing rotor, a tangential rotor, a kneading rotor, a rotor used in an extruder, a roll mill that provides a significant total specific energy, or a creping mill; typically, one or more rotors are used in the mixer, for example, a mixer can incorporate one rotor (e.g., a screw-type rotor), two, four, six, eight, or more rotors. Sets of rotors can be arranged in parallel and / or in consecutive positions within a given mixer configuration.
[0052] For mixing, mixing can be done in one or more mixing steps. Mixing begins when at least one solid elastomer and wet filler are charged into the mixer and energy is added to the mixing system, which drives one or more rotors of the mixer. The one or more mixing steps can occur after the charging step is completed or can overlap with the charging step for any length of time. For example, a portion of one or more solid elastomers and / or wet fillers can be charged into the mixer after mixing begins. The mixer can then be charged with one or more additional portions of solid elastomers and / or fillers and / or crosslinkers. In batch mixing, the charging step is completed before the mixing step is completed.
[0053] Alternatively, control of mixer surface temperature by either mechanism can provide the opportunity for longer mixing or residence times, which can result in improved filler dispersion and / or improved rubber-filler interaction, and / or consistent mixing and / or efficient mixing, as compared to mixing processes without temperature control of at least one mixer surface.
[0054] The temperature control means can be, but is not limited to, the flow or circulation of a heat transfer fluid through a passage in one or more parts of the mixer. For example, the heat transfer fluid can be water or a heat transfer oil. For example, the heat transfer fluid can flow through the rotor, the mixing chamber walls, the ram, and the drop door. In other embodiments, the heat transfer fluid can flow through a jacket (e.g., a jacket with a fluid flow means) or a coil around one or more parts of the mixer. Alternatively, the temperature control means can be an electrical element embedded in the mixer (e.g., providing heat). The system providing the temperature control means can further include a means for measuring either the temperature of the heat transfer fluid or the temperature of one or more parts of the mixer. The temperature measurements can be provided to a system used to control the heating and cooling of the heat transfer fluid. For example, the desired temperature of at least one surface of the mixer can be controlled by setting the temperature of the heat transfer fluid located in a passage adjacent to one or more parts of the mixer, such as the walls, the door, the rotor, etc.
[0055] The temperature of the at least one temperature control means may be set and maintained by one or more temperature control units ("TCU"). This set temperature, or TCU temperature, is referred to herein as "T z In the case of a temperature control means that includes a heat transfer fluid, T z is a measure of the temperature of the fluid itself.
[0056] In one option, the temperature control means may be set to 30°C to 150°C, 40°C to 150°C, 50°C to 150°C, or 60°C to 150°C, e.g., 30°C to 155°C, 30°C to 125°C, 40°C to 125°C, 50°C to 125°C, 60°C to 125°C, 30°C to 110°C, 40°C to 110°C, 50°C to 110°C, 60°C to 110°C, 30°C to 100°C, 40°C to 100°C, 50°C to Temperatures in the range of 100℃, 60℃~100℃, 30℃~95℃, 40℃~95℃, 50℃~95℃, 50℃~95℃, 30℃~90℃, 40℃~90℃, 50℃~90℃, 65℃~95℃, 60℃~90℃, 70℃~110℃, 70℃~100℃, 70℃~95℃, 70℃~90℃, 75℃~110℃, 75℃~100℃, 75℃~95℃, or 75℃~90℃, T z Other ranges are possible with devices available in the art.
[0057] Compared to dry mixing, for the same type of filler, type of elastomer, and type of mixer, the process allows for higher energy input. The controlled removal of water from the mix allows for longer mixing times and thus improves filler dispersion. As described herein, the method provides operating conditions that balance longer mixing times with evaporation or removal of water within a reasonable time.
[0058] Other operating parameters to be considered include the maximum pressure that can be used. The pressure affects the temperature of the filler and rubber mix. If the mixer is a batch mixer equipped with a ram, the pressure inside the mixer chamber can be influenced by controlling the pressure applied to the ram cylinder.
[0059] Alternatively, the rotor tip speed can be optimized. The energy input into the mixing system is at least in part a function of the speed of at least one rotor and rotor type. The tip speed can be calculated according to a formula, taking into account the rotor diameter and rotor speed. Tip speed, m / s=π×(rotor diameter, m)×(rotation speed, rpm) / 60
[0060] The tip speed can vary over the course of mixing, with a tip speed of at least 0.5 m / s or at least 0.6 m / s being obtained for at least 50% of the mixing time, such as at least 60%, at least 70%, at least 75%, at least 80%, at least 85%, at least 90%, at least 95%, or substantially all of the mixing time. The tip speed can be at least 0.6 m / s, at least 0.7 m / s, at least 0.8 m / s, at least 0.9 m / s, at least 1.0 m / s, at least 1.1 m / s, at least 1.2 m / s, at least 1.5 m / s, or at least 2 m / s for at least 50% of the mixing time, or any other portion of the mixing time mentioned above. The tip speed may be selected to minimize mixing time or may be between 0.6 m / s and 10 m / s, between 0.6 m / s and 8 m / s, between 0.6 and 6 m / s, between 0.6 m / s and 4 m / s, between 0.6 m / s and 3 m / s, between 0.6 m / s and 2 m / s, between 0.7 m / s and 4 m / s, between 0.7 m / s and 3 m / s, between 0.7 m / s and 2 m / s, between 0.7 m / s and 10 m / s, between 0.7 m / s and 8 m / s, between 0.7 and 6 m / s, between 1 m / s and 10 m / s, between 1 m / s and 8 m / s, between 1 m / s and 6 m / s, between 1 m / s and 4 m / s, between 1 m / s and 3 m / s, or between 1 m / s and 2 m / s (e.g., for at least 50% of the mixing time, or other mixing times described herein).
[0061] Any combination of commercial mixers equipped with one or more rotors, temperature control means, and other components, and associated mixing methods to produce rubber compounds can be used in the process of the present invention, such as those disclosed in PCT Publication WO2020 / 247663, the disclosure of which is incorporated herein by reference.
[0062] By "one or more mixing steps", it is understood that the processes disclosed herein may include a first mixing step followed by a further mixing step prior to discharge. The one or more mixing steps may be a single mixing step, e.g., a one-stage or single stage mixing step or process, in which the mixing is carried out under one or more of the following conditions: at least one mixing temperature is controlled by a temperature control means, and one or more rotors are operated at a tip speed of at least 0.6 m / s for at least 50% of the mixing time, and / or a temperature of 65° C. or higher, T z and / or continuous mixing, each of which is described in more detail herein. In certain examples, in a single stage or single mixing step, the composite can be discharged with a liquid content of 10% by weight or less. In other embodiments, two or more mixing steps or mixing stages can be performed, so long as one of the mixing steps is performed under one or more of the above conditions.
[0063] As noted above, during one or more mixing steps, in any of the methods disclosed herein, at least some of the liquid present in the mixture and / or the introduced wet filler is removed, at least in part, by evaporation. As an option, one or more mixing steps or stages can further remove a portion of the liquid from the mixture by squeezing, compressing, and / or squeezing, or any combination thereof. Alternatively, a portion of the liquid can be gradually drained from the mixer after or during the composite is discharged.
[0064] During the mixing cycle, after much of the liquid has been released from the composite and mixed fillers, the mix experiences an increase in temperature. It is desirable to avoid excessive temperature increases that could degrade the elastomer. Drainage (e.g., "dumping" in batch mixing) can occur based on time or temperature or specific energy or power parameters to minimize such degradation.
[0065] In any of the methods disclosed herein, a discharge step from the mixer occurs to provide a composite including the filler dispersed in the natural rubber at a total loading of at least 20 phr, e.g., 20 to 250 phr, or other loadings described herein. In one option, the discharge occurs based on a prescribed mixing time. The mixing time between the start of mixing and the discharge can be about 1 minute or more, e.g., about 1 minute to 40 minutes, about 1 minute to 30 minutes, about 1 minute to 20 minutes, or 1 minute to 15 minutes, or 3 minutes to 30 minutes, 5 minutes to 30 minutes, or 5 minutes to 20 minutes, or 5 minutes to 15 minutes, or 1 minute to 12 minutes, or 1 minute to 10 minutes, or other times. Alternatively, in a batch internal mixer, the ram dwell time can be used as a parameter to monitor the batch mixing time, e.g., the time the mixer is operated with the ram in its lowest position, e.g., in a fully locked position or with the ram deflected (as described in PCT Publication WO2020 / 247663, the contents of which are incorporated herein by reference). The ram dwell time can be in the range of 30 minutes or less, 15 minutes or less, 10 minutes or less, or 3 minutes to 30 minutes, or 5 minutes to 15 minutes, or 5 minutes to 10 minutes. As an option, the discharge occurs based on the discharge or discharge temperature. For example, the mixer can have a discharge temperature in the range of 120°C to 190°C, 130°C to 180°C, e.g., 140°C to 180°C, 150°C to 180°C, 130°C to 170°C, 140°C to 170°C, 150°C to 170°C, or other temperatures within or outside those ranges.
[0066] The method further includes discharging the formed composite from the mixer. The discharged composite may have a liquid content of 10% by weight or less, based on the total weight of the composite, as abbreviated by the formula: Liquid content of composite, % = 100 x [mass of liquid] / [mass of liquid + mass of dry composite]
[0067] In any of the methods disclosed herein, the discharged composite can have a liquid content of 10% or less by weight based on the total weight of the composite, e.g., 9% or less, 8% or less, 7% or less, 6% or less, 5% or less, 2% or less, 1% or less by weight based on the total weight of the composite. This amount can range from 0.1% to 10%, 0.5% to 9%, 0.5% to 7%, 0.5% to 5%, or 0.5% to 3% by weight based on the total weight of the composite discharged from the mixer at the end of the process. In any of the methods disclosed herein, the liquid content (e.g., "moisture content") can be the measured weight percent of liquid present in the composite based on the total weight of the composite.
[0068] In any of the methods disclosed herein, the liquid content in the composite can be measured as the mass of liquid present in the composite based on the total mass of the composite. Any number of instruments are known in the art for measuring liquid (e.g., water) content in rubber materials, such as coulometric Karl Fischer titration systems, or moisture balances, such as those manufactured by Mettler (Toledo International, Inc., Columbus, Ohio).
[0069] While in any of the methods disclosed herein the discharged composite has a liquid content of 10% by weight or less, optionally there may be liquid (e.g., water) present in the mixer that is not retained in the discharged composite, this excess liquid is not part of the composite and is not part of any calculated liquid content for the composite.
[0070] In any of the methods disclosed herein, the total liquid content (or total water content or total moisture content) of the material charged into the mixer is greater than the liquid content of the composite discharged at the end of the process. For example, the liquid content of the discharged composite can be 10%-99.9% (wt% to wt%), 10%-95%, or 10%-50% less than the liquid content of the material charged into the mixer.
[0071] Optionally, the process includes adding a crosslinker and optional antidegradants during the filling or mixing, i.e., during one or more mixing steps. In any of the embodiments disclosed herein, alternatively, after mixing of at least the solid elastomer and the wet filler is initiated and prior to the discharging step, the method can further include adding a crosslinker and optional antidegradants to the mixer such that the crosslinker and at least one antidegradant are mixed with the solid elastomer and the wet filler. In one alternative, the mixture consists essentially of the solid elastomer and the wet filler, the mixture consists essentially of the solid elastomer, the wet filler and the antidegradants, the composite consists essentially of the filler dispersed in the elastomer and the antidegradants, the composite consists of the filler dispersed in the elastomer, the composite consists of the filler dispersed in the elastomer and the antidegradants. Alternatively, the addition of the crosslinker and antidegradant can occur before the composite is formed and have a water content of 10% by weight or less, or 5% by weight or less.
[0072] The addition of the crosslinking agent and the optional antidegradant can occur any time before the discharge step, for example before or after the mixer reaches an indicated mixer temperature of 120° C. or higher. This indicated mixer temperature can be measured by a temperature measuring device in the mixing cavity. The indicated temperature of the mixer can be the same as or differ by 30° C. or less, or 20° C. or less, or 10° C. or less, (or 5° C. or less, or 3° C. or less, or 2° C. or less) from the maximum temperature of the mixer or composite obtained during the mixing stage, which can be measured by removing the composite from the mixer and inserting a thermocouple or other temperature measuring device into the composite. In this mixing method, as an option, the crosslinking agent and the optional antidegradant can be added to the mixer when it reaches a temperature of 120° C. or higher. In other embodiments, the indicated temperatures can range from 120°C to 190°C, 125°C to 190°C, 130°C to 190°C, 135°C to 190°C, 140°C to 190°C, 145°C to 190°C, 150°C to 190°C, 120°C to 180°C, 125°C to 180°C, 130°C to 180°C, 135°C to 180°C, 140°C to 180°C, 145°C to 180°C, 150°C to 180°C, 120°C to 170°C, 125°C to 170°C, 130°C to 170°C, 135°C to 170°C, 140°C to 170°C, 145°C to 170°C, 150°C to 170°C, etc.
[0073] Examples of antidegradants that can be incorporated include N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine (6PPD) and others described in other sections herein. Antidegradants can be incorporated in amounts ranging from 1% to 5%, 0.5% to 2%, or 0% to 3%, based on the weight of the composite being formed. Antidegradants added during the filling or mixing step can help prevent degradation during the mixing of the elastomer; however, due to the presence of water in the mixture, the rate of degradation of the elastomer is lower compared to the dry mixing process, and the addition of the antidegradant can be delayed.
[0074] After the composite is formed and discharged, the method may further include the optional step of mixing the composite with an additional elastomer to form a composite comprising a mixture of elastomers. The "additional elastomer" or second elastomer may be an additional natural rubber or may be a non-natural rubber, such as any of the elastomers disclosed herein, such as a synthetic elastomer (e.g., styrene-butadiene rubber (SBR, e.g., SSBR, ESBR, etc.), polybutadiene (BR) and polyisoprene rubber (IR), ethylene-propylene rubber (e.g., EPDM), isobutylene-based elastomers (e.g., butyl rubber), polychloroprene rubber (CR), nitrile rubber (NBR), hydrogenated nitrile rubber (HNBR), polysulfide rubber, polyacrylate elastomers, fluoroelastomers, perfluoroelastomers, silicone elastomers). Mixtures of two or more types of elastomers (mixtures of first and second elastomers) can be used as well, including mixtures of synthetic and natural rubbers or mixtures of two or more types of synthetic or natural rubbers.
[0075] The mixer can be filled with two or more charges of different elastomers to form a composite mixture. For example, the mixer can be filled with natural rubber that has never been dried and at least one additional elastomer, where the at least one additional elastomer is also agglomerated or solid elastomer (e.g., having less than 5% water). Alternatively, the mixer can be filled with an elastomer mixture. Alternatively, the process can include mixing the discharged composite with an additional elastomer to form a mixture. The discharged composite (e.g., single stage or two or more stage mixing) can have a moisture content of 5%, 3%, 2% or less by weight based on the weight of the composite when mixed with one or more additional elastomers (e.g., a composite including carbon black and natural rubber can be mixed with a synthetic elastomer, such as BR or SBR). Furthermore, both elastomers and fillers (wet or dry, e.g., wet or dry carbon black and / or silica and / or silicon-treated carbon black) can be mixed with the composite.
[0076] Alternatively, the composites containing filler (e.g., carbon black and / or silica) and elastomer (e.g., natural rubber and / or SBR and / or BR) prepared by the methods disclosed herein can be mixed with a masterbatch containing natural rubber and / or synthetic polymer made by any method known in the art, such as the known dry blend or solvent masterbatch processes. For example, the silica / elastomer masterbatch can be prepared as described in U.S. Pat. Nos. 9,758,627 and 10,125,229, or can be a masterbatch from neodymium-catalyzed polybutadiene as described in U.S. Pat. No. 9,758,646, the disclosures of which are incorporated herein by reference. The masterbatch can have a fibrous filler, such as poly(p-phenylene terephthalamide) pulp as described in U.S. Pat. No. 6,068,922, the disclosures of which are incorporated herein by reference. The masterbatch can have a filler such as graphene, graphene oxide, reduced graphene oxide, or densified reduced graphene oxide granules, carbon nanotubes, single-walled carbon nanotubes, multi-walled carbon nanotubes, and carbon nanostructures, the latter of which are disclosed in U.S. Pat. No. 9,447,259 and PCT application PCT / US2021 / 027814, the disclosures of which are incorporated herein by reference. Other suitable masterbatches can include composites prepared from wet fillers and solid elastomers, as described in PCT publication WO2020 / 247663, the contents of which are incorporated herein by reference. For example, the masterbatch can have a filler such as carbon black and / or silica and an elastomer such as natural rubber and / or SBR and / or butadiene rubber.Commercially available masterbatches may also be used, such as commercially available masterbatches such as Emulsil™ silica / SBR masterbatch or Emulblack™ carbon black / SBR masterbatch (both available from the Dynasol group).
[0077] Exemplary masterbatches, including elastomer masterbatches (whether the mixture is formed from a first or single stage mix, or from multiple stage mix), include mixtures of natural rubber with synthetic, bio-based, and / or functionalized elastomers (e.g., SSBR, ESBR, BR) where the filler is selected from one or more of carbon black, silica, and silicon-treated carbon black.
[0078] In addition to the solid elastomer, the wetting filler, and the crosslinker, the mixer can be charged with one or more charges of at least one additional elastomer to form a composite mixture. Alternatively, the process can include mixing the discharged composite with an additional elastomer to form a mixture. The at least one additional elastomer can be the same as the solid elastomer or different from the solid elastomer.
[0079] Alternatively, the composite, when discharged, may contain at least one additive selected from antidegradants and crosslinkers (e.g., when the wet filler further contains silica or when dry silica is charged to the mixer), which is added at any time during charging or mixing.
[0080] The carbon black can be untreated or treated carbon black or a mixture thereof. The filler can be or include pellets, fluffy powder, granules, and / or agglomerates. The wet carbon black can be formed into pellets, granules, or agglomerates, for example, in a pelletizer, fluidized bed, or other equipment that creates a wet filler.
[0081] The wet carbon black can be one or more of the following: Undried carbon black, and / or Undried carbon black pellets, and / or dried carbon black that has been rewetted in a pelletizer, for example with water, and / or Dry carbon black that has been ground and rewetted with water in a pelletizer, and / or Dry carbon black mixed with water, and / or Fluffy powder, granules, or agglomerates mixed with water.
[0082] In a typical carbon black manufacture, carbon black is initially prepared as a dry, finely particulate (fluffy) material. This fluffy carbon black can be densified by a conventional pelletizing process, for example, by mixing the carbon black with a liquid, such as adding water, and feeding the mixture to a pin pelletizer. As an option, the liquid can be a solution or dispersion containing a crosslinking agent. Pin pelletizers are well known in the art and include the pin pelletizer described in U.S. Pat. No. 3,528,785. The resulting wet pellets are then heated under controlled temperature and time parameters to remove the liquid from the pellets prior to further handling and shipping. In other processes, carbon black pellets can be produced by a process that omits the drying step. In such processes, the pelletized carbon black contains at least 20% by weight, such as at least 30% by weight, or at least 40% by weight, of process water, based on the total weight of the wet carbon black.
[0083] Alternatively, dried carbon black pellets (e.g., commercially available carbon black pellets) can be rewetted in a pelletizer. The pellets can be granulated, crushed, classified, and / or milled, for example, in a jet mill. The resulting carbon black is in a fluffy form and can be repelletized in a pelletizer or can be otherwise compressed or agglomerated in the presence of water to wet the carbon black. As an option, the carbon black can be repelletized in a pelletizer in the presence of a solution or dispersion containing a crosslinker. Alternatively, the fluffy carbon black can be compressed into other shapes, for example, in the shape of square blocks, in equipment known in the art. Alternatively, the carbon black, for example, carbon black pellets or fluffy carbon black, can be wetted, for example, by using a fluidized bed, a sprayer, a mixer, or a rotating drum. When the liquid is water, the undried or rewetted carbon black can have a water content of 20% to 80%, 30% to 70%, or other ranges, such as 55% to 60%, by weight, based on the total weight of the wet carbon black.
[0084] The carbon black can be furnace black, gas black, thermal black, acetylene black, or lamp black, plasma black, recycled carbon black (e.g., as defined in ASTM D8178-19), or carbon products including silicon-containing and / or metal-containing species.
[0085] The carbon black used in any of the methods disclosed herein may be reinforcing carbon black, semi-reinforcing carbon black, or e.g., 20m 2 / g~250m 2Other carbon blacks may be used having a statistical thickness surface area (STSA) in the range of 100 / g or more. STSA (statistical thickness surface area) is measured based on ASTM test procedure D-5816 (measured by nitrogen adsorption). Examples of reinforcing grades of the ASTM grade include N110, N121, N134, N220, N231, N234, N299, N326, N330, N339, N347, N351, N358, and N375 carbon black. Examples of semi-reinforcing grades of the ASTM grade include N539, N550, N650, N660, N683, N762, N765, N774, N787, N990 carbon black, and / or N990 grade thermal black.
[0086] Carbon black, for example, is 20m 2 / g~250m 2 The carbon black may have any other carbon black having a statistical thickness surface area (STSA) in the range of 2000 to 30000 / g or more. STSA (Statistical Thickness Surface Area) is measured according to ASTM Test Procedure D-5816 (measured by nitrogen adsorption). The carbon black may have a compressed oil absorption (COAN) in the range of about 30 mL / 100 g to about 150 mL / 100 g. COAN is measured according to ASTM D3493. In one option, the carbon black may have a statistical thickness surface area (STSA) in the range of 2000 to 30000 / g or more. 2 / g~180m 2 / g, or 60m 2 / g~150m 2 / g range, and a COAN in the range of 40mL / 100g to 115mL / 100g or 70mL / 100g to 115mL / 100g.
[0087] As mentioned above, the carbon black can be rubber black, for example, reinforcing grade carbon black or semi-reinforcing grade carbon black. Carbon blacks sold under the trademarks Regal®, Black Pearls®, Spheron®, Sterling®, Propel®, Endure®, and Vulcan® available from Cabot Corporation, Raven®, Statex®, Furnex®, and Neotex®, as well as CD and HV series available from Birla Carbon (previously available from Columbian Chemicals), and Corax®, Durax®, Ecorax®, and Purex® CK series available from Orion Engineered Carbons (previously available from Evonik and Degussa Industries), as well as other suitable fillers used in rubber or tire applications can also be utilized for use with various implementations. Suitable chemically functionalized carbon blacks include those disclosed in International Publication WO 96 / 18688 and U.S. Patent Application Publication No. 2013 / 0165560, the disclosures of which are incorporated herein by reference. Mixtures of any of these carbon blacks can be used.
[0088] Any of the methods disclosed herein relate, in part, to a method of preparing a composite that includes at least two mixing steps or stages, which two (or more) mixing steps can be considered to be multi-step or multi-stage mixing, with a first mixing step or stage and at least a second mixing step or stage. The one or more stage mixing process can be batch, continuous, semi-continuous, and combinations thereof.
[0089] In a multi-step process, the method for preparing a composite includes the step of charging or introducing into a first mixer at least a) one or more solid elastomers, b) one or more fillers, where at least one filler or at least a portion of the filler is a wet filler as described herein (e.g., a wet filler that includes the filler and a liquid present in an amount of at least 20% by weight based on the total weight of the wet filler), and an optional c) crosslinker. The step of mixing the solid elastomer with the wet filler and optionally the crosslinker forms a mixture or composite during this mixing step, which can be considered the first step or stage. The method further includes mixing the mixture during this first mixing step to an extent that at least a portion of the liquid is removed by evaporation or by an evaporation process that occurs during mixing. The first mixing step (in one or more mixing steps) or stage is carried out using one or more of the aforementioned processes to form a composite, it being understood that after completion of the first mixing, the mixture discharged from the mixer (e.g., the discharged mixture) after the first mixing step need not have a liquid content of 10% by weight or less. In other words, in a multi-stage process, the mixture from the first mixer (or first mixing step) resulting from completion of the first mixing can have a liquid content of more than about 10% by weight, but has a reduced liquid content (in weight %) compared to the liquid content of the mixed solid elastomer and wet filler at the start of the first mixing step.
[0090] As a further option, there can be a dwell time before the first mixer or other mixer is used in a second mixing step, where the composite formed from the first mix remains and / or cools in the first mixer or other container or location (e.g., mix, stop, and then further mix). For example, the dwell time can be such that the mixture obtains a temperature (also referred to as a probe temperature) of less than 180°C before the further mixing step begins (e.g., the discharged mixture can have a material temperature in the range of about 100°C to about 180°C, or about 70°C to 179°C, or about 100°C to about 170°C, or about 120°C to about 160°C). Alternatively, the dwell time before the further or second mixing step begins can be from about 1 minute to 60 minutes or more. The material temperature can be obtained by many methods known in the art, such as by inserting a thermocouple or other temperature measuring device into the mixture or composite.
[0091] The method further includes mixing or further mixing the mixture in at least a second mixing step or stage using the same mixer (i.e., the first mixer) and / or using a second mixer different from the first mixer. In a multi-stage mixing process, there is the option of charging the crosslinker into either the first mixer, the second mixer, or both.
[0092] Further mixing steps performed in multi-stage mixing after the first mixing can use any one or more of the mixing procedures or parameters used in the first mixing step described herein. Thus, in performing the further mixing steps or stages, the same or different mixer design and / or the same or different operating parameters can be used in the further mixing steps as the first mixer. The mixers and options thereof described above for the first mixing step and / or the operating parameters described above for that mixing step can optionally be used in the further or second mixing steps (e.g., the mixing step can be performed using a tip speed of at least 0.5 m / s for at least 50% of the time or a tip speed of at least 0.6 m / s for at least 50% of the time, as described herein, and / or a T of 65° C. or greater, among other parameters disclosed herein or disclosed in PCT Publication WO2020 / 247663). z may include.
[0093] In a multi-stage process, the second mixing step (second stage mixing) can also include charging other ingredients to the mixer in addition to the mixture discharged from the first mixing step. For example, if the crosslinker is not charged to the first mixer, the crosslinker can be charged to the second mixer, for example, as a separate charge or as a mixture (particulate mixture or co-pellet) with a filler (wet or dry filler, the same or different from that charged to the first mixer). Additionally or alternatively, by way of example, the method can include charging an additional filler, such as a dry filler, a wet filler, or a mixture thereof, before or during the second mixing step. The additional filler can be the same or different from the filler already present in the mixture, such as any additional filler disclosed herein. For example, the mixture discharged from the first mixer can be considered a masterbatch, in which either all or a portion is mixed with the additional filler. For example, wet or dry carbon black, silica, silicon-treated carbon black (and mixtures thereof) can be added to the mixture discharged from the first mixing step, e.g., a mixture containing carbon black and natural rubber.
[0094] In the multi-stage mixing process, at least one option is to use at least a second mixer in the further mixing step. When this option is used, the second mixer can have the same or different design as the first mixer, and / or can have the same or one or more different operating parameters as the first mixer. Specific examples are provided below for the first and second mixer options, without limitation. For example, the first mixer can be a tangential mixer or an intermeshing mixer, and the second mixer can be a tangential mixer, an intermeshing mixer, an extruder, a kneader, or a roll mill. For example, the first mixer can be an internal mixer, and the second mixer can be a kneader, a single screw extruder, a twin screw extruder, a multi-screw extruder, a continuous compounder, or a roll mill. For example, the first mixer can be a first tangential mixer, and the second mixer can be a second (different) tangential mixer. For example, a first mixer is operated with a ram and a second mixer is operated without a ram, For example, a second mixer is used and operated at a mixture fill level ranging from 25% to 70%, 25% to 60%, 25% to 50%, 30% to 50%, or other fill levels described herein, on a dry weight basis.
[0095] As an alternative, the method includes mixing or further mixing the mixture in at least a second mixing step or stage using the same mixer (i.e., the first mixer) and / or using a second mixer different from the first mixer. Mixing in the second mixer can be such that the second mixer or second mixer is operated with a ram pressure of 5 psi or less, and / or with the ram raised to at least 75% of the highest ram level (e.g., at least 80%, at least 90%, at least 95%, or at least 99%, or 100% of the highest ram level), and / or with a ram operated in a floating mode, and / or with a ram positioned such that the ram does not substantially contact the mixture, and / or with a mixer without a ram, and / or with a fill factor of the mixture ranging from 25% to 70%. The method further includes discharging the formed composite from the last mixer used such that the composite has a liquid content of 10% by weight or less based on the total weight of the composite. Methods for the operation of the second mixer that are suitable are described in PCT Publication WO2020 / 247663, the disclosure of which is incorporated herein by reference.
[0096] Additives can be mixed in during the mixing and / or compounding process (e.g., either in a single stage mix, or in the second or third stage of a multi-stage mix), and can include antidegradants, and one or more rubber chemicals that enable dispersion of the filler in the elastomer. Rubber chemicals as defined herein include processing aids (e.g., various oils and plasticizers, waxes, to facilitate mixing and processing of the rubber), activators (e.g., zinc oxide and fatty acids, to activate the vulcanization process), accelerators (e.g., sulfenamides and thiazoles, to accelerate the vulcanization process), vulcanizing agents (or curing agents, e.g., sulfur, peroxides, to crosslink the rubber), and other rubber additives, such as, but not limited to, vulcanization retarders, crosslinking coagents, peptizers, adhesion promoters (e.g., the use of cobalt salts to promote adhesion of steel coats to rubber-based elastomers (e.g., as disclosed in U.S. Pat. No. 5,221,559 and U.S. Patent Application Publication No. 2020 / 0361242, the disclosures of which are incorporated herein by reference), resins (e.g., tackifiers, traction resins, The rubber chemicals may include one or more of: tungsten carbide resins, flame retardants, colorants, foaming agents, and heat reducing additives (HBUs). In one alternative, the rubber chemicals may include processing aids and activators. In another alternative, the one or more other rubber chemicals may be selected from: zinc acid value, fatty acids, zinc salts of fatty acids, waxes, accelerators, resins, and process oils. Exemplary resins include one or more of C5 resins, C5-C9 resins, C9 resins, rosin resins, terpene resins, aromatic modified terpene resins, dicyclopentadiene resins, alkylphenol resins, and resins disclosed in U.S. Pat. Nos. 10,738,178, 10,745,545, and U.S. Patent Publication No. 2015 / 0283854, the disclosures of which are incorporated herein by reference.
[0097] In any of the methods for making the composite material disclosed herein, the method may further comprise, after formation of the composite material, one or more of the following steps: one or more holding steps, One or more drying steps can be used to further dry the composite to obtain a dry composite; one or more extrusion processes, one or more calendering steps, one or more milling steps to obtain a milled composite material, one or more granulation steps, one or more cutting steps, one or more baling steps to obtain a baled product or mixture, one or more bale mixtures or products are broken down to form a granulated mixture; and / or one or more mixing or blending steps, and / or One or more sheeting processes.
[0098] As a further example, the following sequence of steps may occur, and each step may be repeated any number of times (with the same or different settings) after formation of the composite. one or more holding steps to further improve elasticity, one or more cooling steps, drying the composite to obtain a further dried composite, mixing or blending the composite materials to obtain a blended mixture, milling the blended mixture to obtain a milled mixture; Granulation of the milled mixture; Optionally, baling the mixture after granulation to obtain a baled mixture. Optionally, breaking down and mixing the baled mixture.
[0099] Additionally or alternatively, the composites can be compounded with one or more of antidegradants, zinc oxide, fatty acids, zinc salts of fatty acids, waxes, accelerators, resins, processing oils, and / or curing agents and vulcanized to form vulcanizates. Such vulcanized compounds can have one or more improved properties, such as one or more improved rubber properties, such as, but not limited to, improved hysteresis, abrasion resistance, and / or rolling resistance, e.g., in tires, or improved mechanical and / or tensile strength, or improved tan delta and / or improved tensile stress ratio.
[0100] As an example, in the compounding step, the ingredients are mixed with the neat composite in a mixing device, except for the sulfur or other crosslinking agent and accelerator (non-vulcanizing and / or antidegradants are often premixed and collectively referred to as "smalls"). The most common mixing device is an internal mixer, such as a Banbury or Brabender mixer, however other mixers, such as continuous mixers (e.g. extruders), can also be used. Thereafter, in a later or second compounding step, the crosslinking agent, such as sulfur, and accelerators (if required) (collectively referred to as vulcanizing agents) are added. Alternatively, the compounding step can include mixing the composite with one or more of the antidegradants, zinc oxide, fatty acids, zinc salts of fatty acids, waxes, accelerators, resins, processing oils, and curing agents in a single compounding stage or step, e.g. the vulcanizing agents can be added with the smalls in the same compounding step. The compounding step is often performed in the same type of equipment as the mixing step, however it can be performed in a different type of mixer or extruder or roll mill. Those skilled in the art will appreciate that once the vulcanizing agent is added, vulcanization will begin once the proper activation conditions for the crosslinking agent are reached. Thus, when sulfur is used, the temperature during mixing is preferably maintained substantially below the vulcanization temperature.
[0101] Also disclosed herein is a method of making a vulcanizate, the method including at least the step of curing the composite in the presence of at least one curative, the curing being accomplished by application of heat, pressure, or both, as is known in the art.
[0102] For this vulcanizate, the vulcanizate can have one or more elastomeric properties, for example, the vulcanizate can have a tensile stress ratio M300 / M100 of at least 5.9, e.g., at least 6.0, at least 6.1, at least 6.2, as assessed by ASTM D412, where M100 and M300 represent the tensile stresses at 100% and 300% elongation, respectively.
[0103] Alternatively, or in addition, the vulcanizate may have a tan δ(60° C.) of 0.22 or less, such as 0.21 or less, 0.2 or less, 0.19 or less, 0.18 or less, such as 0.16 or less, 0.15 or less, 0.14 or less, 0.13 or less, 0.12 or less, or 0.11 or less.
[0104] Vulcanizates prepared from the present invention (e.g., made by any of the processes disclosed herein for mixing wet fillers, solid elastomers, and crosslinkers, whether in a single stage or multiple stages, under the disclosed mixing conditions of Tz or tip speed) can exhibit improved properties. For example, vulcanizates prepared from the composites of the present invention can have improved properties over vulcanizates made from composites made by dry mixing solid elastomers, non-wetting fillers, and crosslinkers ("dry-mixed composites"), particularly dry-mixed composites having the same composition ("dry-mixed equivalents"). Thus, comparisons were made between comparable fillers, elastomers, filler loadings (e.g., ±5% by weight, ±2% by weight) and formulations (including crosslinkers), and optional curatives, between the dry mix and the mixing processes of the present invention. Under those conditions, the vulcanizates have tan δ values that are less than the tan δ values of vulcanizates prepared from dry-mixed composites having the same composition. Additionally or alternatively, the vulcanizate has a tensile stress ratio, M300 / M100, greater than the tensile stress ratio of a vulcanizate prepared from a dry blend composite having the same composition, where M100 and M300 represent the tensile stresses at 100% and 300% elongation, respectively.
[0105] Elastomers (e.g., diene-based elastomers) are known to degrade in the presence of air / oxygen. Degradation can occur in the form of polymer chain scission and / or crosslinking, which can affect rubber properties. Elastomer composites can be cured in the presence of curing agents, e.g., sulfur, to affect crosslinking, resulting in a vulcanizate that is cured (for the composite) and has greater stability against degradation, but degradation can still occur, but to a lesser extent compared to the uncured composite. However, it may be necessary to store (and / or transport) uncured elastomer composites for extended periods of time (e.g., 3, 6, 9 months, or up to 1 year, or even up to 2 years). Furthermore, the elevated temperatures often present in warehouses or during transport (trucks, shipping containers) can accelerate the rate of degradation. To slow this rate, the composites can be stored in refrigerators or under air conditioning. Such storage solutions, however, require excessive energy consumption and refrigeration equipment.
[0106] Composites containing crosslinkers can exhibit reduced degradation over time, for example, at least 5 days or more, at least 1 week, at least 2 weeks, at least 1 month (at least 30 days), at least 2 months, at least 30 months, and even at least 6 months (at least 180 days), up to 1 year (12 months), or even up to 2 years at a temperature of at least 20° C. Such composites that have been stored or aged are referred to as “aged composites.” Alternatively, the aged composites can be stored or aged at elevated temperatures for at least 1 day. Degradation of aged composites can be observed by monitoring the rubber properties of the composites or vulcanizates. For example, vulcanizates prepared from composites made with crosslinkers according to the processes disclosed herein have certain properties that are maintained over time. Aging the composites disclosed herein for a period of at least 1 day, such as 5 days, up to 1 year, can result in improved hysteresis properties of vulcanizates prepared from the aged composites, as indicated by a maximum tan δ, Payne effect, and / or Payne ratio value increased by 10% or less over values of vulcanizates prepared from the composites that have not been aged, e.g., aged for 2 days or less, or 1 day or less. For example, the rheological properties of the composites (and compounds formed from such composites) can be enhanced. One example of such a property is the Payne effect of the vulcanizate, which can be indicated by the Payne ratio or Payne difference. The Payne ratio is defined as G'(0.1%) / G'(50%), where G'(0.1%) is the dynamic storage modulus measured at a strain amplitude of 0.1%, and G'(50%) is the dynamic storage modulus measured at a strain amplitude of 50%. The Payne difference is the difference between G'(0.1%) and G'(59%).
[0107] At room temperature (e.g., 20° C.), the aged composite can be stored or aged for at least 5 days, or other time periods disclosed herein. The time of aging can be determined from the date of manufacture (day 0). As an option, the aged composite has been stored or aged at a temperature of at least 20° C., e.g., 20° C. to 200° C., or under ambient conditions, e.g., a temperature range of 20° C. to 40° C., or 20° C. to 30° C., either in a temperature and humidity controlled environment or without temperature and humidity control (e.g., warehouse, truck). The time of aging can be at least 7 days, at least 2 weeks, at least 1 month, at least 3 months, at least 6 months, or at least 1 year or more, e.g., 5 days to 2 years, 5 days to 1 year, 5 days to 6 months, 5 days to 3 months, 2 weeks to 1 year, 2 weeks to 6 months, 1 month to 1 year, 1 month to 6 months, and other ranges.
[0108] As an option, the aged composite can be stored or aged at an elevated temperature for at least one day, e.g., at a temperature of at least 40°C, e.g., at a temperature in the range of 40°C to 200°C, 40°C to 180°C, 40°C to 150°C, 40°C to 120°C, 40°C to 100°C, 40°C to 90°C, 40°C to 75°C, 50°C to 200°C, 50°C to 180°C, 50°C to 150°C, 50°C to 120°C, 50°C to 100°C, 50°C to 90°C, 50°C to 75°C, 60°C to 200°C, 60°C to 180°C, 60°C to 150°C, 60°C to 120°C, 60°C to 100°C, or 60°C to 90°C. In certain embodiments, the composite can be stored or aged at elevated temperature for at least 7 days, at least 2 weeks, at least 3 weeks, or at least 1 month, up to 6 months, or up to 1 year. As an alternative, storage at elevated temperature is for up to 1 month, up to 2 weeks, or up to 1 week, e.g., storage for 5 days to 1 month.
[0109] Also disclosed herein are articles made from or including the composites or vulcanizates disclosed herein.
[0110] The composites can be used to make elastomer or rubber-containing products. As an option, the elastomer composites can be used or manufactured for use in forming vulcanizates that are incorporated into various tire components, such as tire treads (e.g., on-road or off-road tire treads), caps and bases, undertreads, innerliners, tire sidewalls, tire carcasses, tire sidewall inserts, tire wire skim, and mountain tire cushion gums, in pneumatic and non-pneumatic or solid tires. Alternatively, or in addition, the elastomer composites (and the subsequent vulcanizates) can be used in hoses, seals, gaskets, weatherstripping, windshield wipers, automotive parts, liners, pads, housings, wheel and truck elements, tire sidewall inserts, tire wire skim, and mountain tire cushion gums, in pneumatic and non-pneumatic or solid tires. Alternatively, or in addition, the elastomeric composites (and subsequent vulcanizates) can be used in a variety of applications, such as hoses, seals, gaskets, vibration isolation articles, trucks, tracked propulsion systems, such as track pads for bulldozers, engine mounts, earthquake resistance, mining equipment, such as screens, linings for mining equipment, conveyor belts, chute liners, slurry pump liners, mud pump parts, such as impellers, valve seats, valve bodies, piston hubs, piston rods, plungers, and a variety of applications, such as mixing slurries and slurry pump inlets. The compositions may be used in impellers for impellers, grinding mill liners, cyclones and hydrocyclones, expansion joints, marine equipment such as linings for pumps (e.g., dredge pumps and outboard motor pumps), hoses (e.g., dredge hoses and outboard motor hoses) and other marine equipment, shaft seals for marine, oil, aerospace and other applications, propeller shafts, linings for transport pipes such as oil sands and / or tar sands, and other applications where wear resistance and / or improved dynamic properties are required.Additionally, the elastomeric composites, via the vulcanized elastomeric composites, can be used in rollers, cams, shafts, pipes, vehicle bushings, or other applications where wear resistance and / or improved dynamic properties are required.
[0111] Thus, the articles include vehicle tire treads, such as caps and bases, sidewalls, undertreads, innerliners, wire skims, tire carcasses, engine mounts, bushings, conveyor belts, vibration isolators, weatherstripping, windshield wipers, automotive parts, seal gaskets, hoses, liners, pads, housings, and wheel and track elements. For example, the article can be a multi-component tread, such as those disclosed in U.S. Patent Nos. 9,713,541, 9,713,542, 9,718,313, and 10,308,073, the disclosures of which are incorporated herein by reference. EXAMPLES
[0112] The mixing steps of Examples I and II, as well as all compounding processes, were carried out in a BR-1600 Banbury® mixer ("BR1600; Manufacturer: Farrell") at a ram pressure of 2.8 bar. The BR1600 mixer was operated with two 2-wing, tangential rotors (2WL) giving a capacity of 1.6 L. The mixing step of Example III was carried out in a BB-16 tangential mixer ("BB-16"; Kobelco Kobe Steel Group) fitted with two tangential 4-wing rotors (Model 4WN) giving a capacity of 16.2 L.
[0113] The water content in the discharged composite was measured using a moisture balance (Model: HE53; Manufacturer: Mettler Toledo NA, Ohio). The composite was sliced into small pieces (size: length, width, height <5mm) and 2-2.5g of material was placed on a disposable aluminum disc / plate, which was placed inside the moisture balance. The mass loss was recorded for 30 minutes at 125°C. At the end of the 30 minutes, the moisture content of the composite was recorded as follows:
number
[0114] The following tests were used to measure the rubber properties of each vulcanizate. · The tensile stress at 100% elongation (M100) and 300% elongation (M300) were evaluated according to ASTM D412 (Test Method A, Die C) at 23°C, 50% relative humidity, and a crosshead speed of 500 mm / min. An extensometer was used to measure the tensile strain. The ratio of M300 / M100 is called the tensile stress ratio (or elasticity ratio). · Maximum tan δ was measured in torsion mode with an ARES-G2 rheometer (manufacturer: TA Instruments) in a parallel plate configuration with a diameter of 8 mm. The diameter size of the vulcanizate specimens was 8 mm diameter and approximately 2 mm thick. The rheometer was operated at a constant temperature of 60 °C and at a constant frequency of 10 Hz. Strain sweeps were performed with strain amplitudes of 0.1 to 68%. Measurements were performed at 10 points per decade and the maximum measured tan δ ("max tan δ") was recorded and is also denoted as "tan δ" unless otherwise stated. The Payne ratio was calculated from the ratio of the dynamic storage modulus G' at 0.1% strain to the dynamic storage modulus G' at 50% strain, i.e., G'(0.1%) / G'(50%). Example I
[0115] This example describes the preparation of a composite and the corresponding vulcanizate, in which a solid elastomer was mixed with a wetting filler and a crosslinker.
[0116] All samples were prepared with ASTM grade N234 carbon black, provided as VULCAN® 7H carbon black ("V7H"; Cabot Corporation). Wet carbon black pellets had a moisture content of 55.2% and were prepared by milling in an 8-inch model MicroJet mill to produce fluffy carbon black particles with a 99.5% particle size diameter of less than 10 microns. The fluffy carbon black was then wetted in a pin pelletizer to regenerate the wetted pellets. The elastomer used was standard grade SMR5 natural rubber (Hokson Rubber, Malaysia). Technical descriptions of this natural rubber are widely available, for example in the Blue Book of Rubber World Magazine, published by Lippincott and Peto, Inc. (Akron, Ohio, USA). The cross-linker used was sodium (2Z)-4-[(4-aminophenyl)amino]-4-oxo-2-butenoate, commercially available as Sumilink® 200 cross-linker ("S200", Sumitomo Chemical).
[0117] Two examples were prepared where the crosslinker was added at the same mixing stage as the wet carbon black. The following comparative examples were prepared: conventionally mixed natural rubber and carbon black (Dry 1), conventionally mixed natural rubber, carbon black and S200 (Dry 2).
[0118] The formulation is shown in Table 1. The carbon black loading was set on a dry basis. [Table 1]
[0119] 6PPD = N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine The wax beads are Akrowax™ 5031 wax beads and BBTS (N-tert-butyl-2-benzothiazole sulfenamide) is the accelerator BBTS, all available from Akrochem (Akron, Ohio).
[0120] The experimental records for the first stage are outlined in Table 2 (dry mix) and Table 3 (mix with wet filler). The time intervals listed in the mix methods below represent the time from the start of mixing defined as "0 s". In Example 1, the crosslinker was added at a temperature of 140°C, and in Example 2, the crosslinker was added for a total mix time of 210 seconds. [Table 2] [Table 3]
[0121] All composites were sheeted on a two-roll mill operated at 50° C. and about 37 rpm, then passed six times with a nip spacing of about 5 mm. For both Example 1 and Example 2 after Stage 1 mixing, the moisture content was 0.8% and 0.9%, respectively, based on the weight of the composite.
[0122] Vulcanizates were formed by compounding the composite with the Stage 2 formulation according to the procedure in Table 4, followed by compounding with the curative (Stage 3 formulation) according to the procedure in Table 5. After each compounding step, the compound was sheeted on a two-roll mill operated at 50° C. and about 37 rpm, followed by six passes with a nip spacing of about 5 mm. The final compound was sheeted to a thickness of 2.4 mm on a two-roll mill operated at 60° C. The final compound was cured in a heated press (2500 lbs) at 150° C. for 30 minutes. [Table 4] [Table 5]
[0123] The properties of the vulcanizates are shown in Table 6. [Table 6]
[0124] The data in Table 6 show that the dynamic hysteresis loss, maximum tan δ, of the composites mixed with wet filler and crosslinker was lower than the comparative Dry 1 and Dry 2 examples. The tensile stress ratios, M300 / M100, of Examples 1 and 2 were higher than those of the dry mixed examples. This shows that improved rubber properties can be obtained by combining mixing with wet filler and the use of crosslinkers. Example II
[0125] This example describes the preparation of a composite and the corresponding vulcanizate, in which a solid elastomer was mixed with a wet filler that was co-pelletized with a crosslinker.
[0126] Three crosslinkers were evaluated: cystamine dihydrochloride ("Cystamine"; 96%, Sigma-Aldrich), hexamethylene-1,6-bis(thiosulfate ("Duralink"; Duralink™ HTS tire additive, Eastman Chemical Co.), and thiourea (Sigma-Aldrich). All samples were prepared with ASTM grade N234 carbon black, provided as VULCAN® 7H carbon black ("V7H"; Cabot Corporation). The elastomer used was natural rubber, standard grade SMR20 (Hokson Rubber, Malaysia). Technical descriptions of this natural rubber are widely available, for example in the Blue Book of Rubber World Magazine, published by Lippincott and Peto, Inc. (Akron, Ohio, USA).
[0127] Co-pellets containing crosslinker and carbon black (wet or dry) were charged into a mixer. Co-pellets of crosslinker and carbon black were formed by mixing a solution of 6 g of crosslinker in DI water (310 g) and 250 g of fluffy V7H carbon black prepared in Example I. Pelletization was performed at 60° C. with a 5 minute residence time in a 10 HP heated pin pelletizer. In Examples 3, 4, and 5, the resulting wet filler was used without drying. For example, in Dry 3, Dry 4, and Dry 5, the resulting wet pellets were dried in an oven at 125° C. overnight prior to mixing. In comparative Example Dry 6, pellets containing carbon black and no crosslinker were prepared as described in this example.
[0128] The formulations are shown in Table 7. [Table 7]
[0129] 6PPD = N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine The wax beads are Akrowax™ 5031 wax beads and CBS is N-cyclohexyl-2-benzothiazole sulfenamide, all available from Akrochem, Akron, Ohio.
[0130] For all mixes with dry fillers (i.e., Dry 6 and Dry 3 through Dry 5), the mix procedure is shown in Table 8. [Table 8]
[0131] The procedure for mixing the wet co-pellets Examples 3, 4 and 5 is shown in Table 9. [Table 9]
[0132] The moisture content of Examples 3, 4 and 5 after Stage 1 mixing was 0.74%, 0.35% and 0.55%, respectively, based on the weight of the composite. All composites were subjected to a second compounding stage (procedure in Table 10) in which hardeners and smalls (for composites from wet co-pellets; hardeners only for dry mixed composites) were added. [Table 10]
[0133] The compound was sheeted on a two-roll mill operated at 50° C. and approximately 27 rpm, gathered for 1 minute, and then passed four times with a nip separation of approximately 5 mm. The compound was sheeted to a thickness of 2.4 mm on a two-roll mill operated at 60° C. The final compound was cured in a heated press at a temperature of 150° C. (2500 lbs) for 21 minutes. The properties of the vulcanizate are shown in Table 11. [Table 11]
[0134] From the data in Table 11, it can be seen that the composite vulcanizates prepared from the wet co-pellets containing crosslinker exhibited either a lower maximum tan δ, a higher tensile stress ratio (M300 / M100), or both, compared to the corresponding comparative dry mixed examples. The vulcanizates of Examples 3, 4, and 5 all exhibited both a lower maximum tan δ and a higher tensile stress ratio than Comparative Example Dry 6. Example III
[0135] This example describes the preparation of a composite by mixing the wet composite with natural rubber and a vulcanizing agent, and the evaluation of the properties of the composite and compounds prepared from the composite.
[0136] All samples were prepared with ASTM grade N234 carbon black provided as VULCAN® 7H carbon black ("V7H"; Cabot Corporation). Wet carbon black pellets had a moisture content of 56% and were prepared by milling in an 8-inch model MicroJet mill to produce fluffy carbon black particles with a 99.5% particle size diameter of less than 10 μm. The fluffy carbon black was then wetted in a pin pelletizer and regenerated into wet pellets. The elastomer used was standard grade RSS3 natural rubber (Von Bundit Co. Ltd., Thailand). Technical descriptions of this natural rubber are widely available, for example in the Blue Book of Rubber World Magazine published by Lippincott and Peto, Inc. (Akron, Ohio, USA). The crosslinker used was sodium (2Z)-4-[(4-aminophenyl)amino]-4-oxo-2-butenoate, commercially available as Sumilink® 200 crosslinker ("S200"; Sumitomo Chemical).
[0137] The mixing of the wet carbon black with the natural rubber was carried out as a two-stage mix followed by a two-stage compounding. The formulations used are shown in Table 12. The carbon black loadings were set on a dry basis. [Table 12]
[0138] The two-stage mixing procedure is outlined in Table 13 (first stage) and Table 14 (second stage). The time intervals listed in the mixing methods below represent process times. All mixing was performed under the following conditions: TCU temperature = 90°C, fill rate = 66%, ram pressure = 112 bar G. The first stage mixing was performed in a BB-16 mixer (16.2 L capacity) fitted with a 4WN rotor at a ram pressure of 112 bar G and is outlined in the procedure in Table 13. After the first stage mixing, the composite was processed in a TSR-1252 axial screw discharge extruder (Kobelco Kobe Steel Group) fitted with a stationary knife.
[0139] The second stage mixing was done in a BB-16 mixer (14.4 L capacity) fitted with a 6WI rotor, following the procedure in Table 13. Mixing was done with the ram raised to its highest position. After initial mastication, the mixture was run under PID (proportional integral derivative) control, which allows automatic control of batch temperature through a feedback loop. A thermocouple inserted through the mixer drop door measured the batch temperature and transmitted it to the PID controller. The controller output was used to control the mixer rotor speed. The second stage mixing conditions were TCU temperature = 65°C, fill rate = 35%, and mix time = 582 seconds. [Table 13] [Table 14]
[0140] The moisture content of the composite after the first stage mixing was 4.96% and after the second stage mixing it was 0.51%. The second stage composite was processed in a TSR-1252 twin screw discharge extruder (Kobelco Kobe Steel Group) equipped with a roller die. The resulting sheet was cooled under ambient air.
[0141] The composites were stored in air for 30 or 180 days. After the storage period, vulcanizates were formed by compounding the composite with the Stage 3 formulation according to the procedure in Table 15, and then compounding with the curative (Stage 4 formulation) according to the procedure in Table 16. After each compounding step, the composites were sheeted on a two-roll mill operated at 50° C. and 37 rpm, then with six passes at a nip spacing of about 2 mm. The final compound was sheeted to a thickness of 2.4 mm on a two-roll mill operated at 60° C. The final compound was cured in a heated press (2500 lbs) at 150° C. for 30 minutes. [Table 15] [Table 16]
[0142] The properties of the vulcanizates prepared from two samples each of the composite samples aged for 30 days (Examples 6 and 7) and 180 days (Examples 8 and 9) are shown in Table 17. [Table 17]
[0143] As can be seen from the data in Table 17, the properties of the vulcanizates prepared from the aged composites containing a vulcanizing agent were surprisingly similar whether the composites were stored for 30 days (Examples 6 and 7) or 180 days (Examples 8 and 9). Even more surprisingly, the maximum tan δ values remained unchanged for all vulcanizates. The data indicate that crosslinkers can help reduce the degradation of composite performance over time, for example, up to at least 180 days.
[0144] Use of the terms "a" and "an" and "the" should be understood to include both the singular and the plural unless otherwise indicated or clearly contradicted by context. The terms "comprising," "having," "including," and "containing" should be understood to be open ended (i.e., meaning "including, but not limited to") unless otherwise indicated. The recitation of ranges of values herein is merely intended to serve as a shorthand method of independently expressing each individual value falling within the range, unless otherwise indicated herein, and each individual value is incorporated into the specification as if it were independently set forth herein. All methods described herein can be performed in any suitable order unless otherwise indicated herein or otherwise clearly contradicted by context. The use of any and all examples or exemplary terms provided herein (e.g., "for example") are merely intended to better clarify the invention and do not pose a limitation on the scope of the invention unless otherwise indicated. No language in the specification should be construed as indicating any non-claimed element essential to the practice of the invention. The present invention includes the following aspects. (1) The following steps: (a) charging a mixer with a wet filler comprising at least a solid elastomer, carbon black, and a liquid present in an amount of at least 20% by weight based on the total weight of the wet filler, and a crosslinker; (b) mixing, in one or more mixing steps, the at least solid elastomer, the wetting filler, and the crosslinker to form a mixture and removing at least a portion of the liquid from the mixture by evaporation; and (c) discharging from the mixer the composite including the filler dispersed in the elastomer at a loading of at least 20 phr, wherein the composite has a liquid content of 10% by weight or less, based on the total weight of the composite; wherein the crosslinking agent is selected from compounds having at least two functional groups; The first functional group is -N(R 1 )(R 2 ), -N(R 1 )(R 2 )(R 3 ) + A - , -S-SO 3 M 1 and structures represented by formula (I) and formula (II),
change
change
change
Claims
1. A method for preparing a composite material comprising the steps of: (a) charging a mixer with at least a solid elastomer, a wet filler comprising a liquid present in an amount of at least 20% by weight based on the total weight of the wet filler, and carbon black, and a crosslinker, wherein the wet filler is in the form of a powder, paste, pellets, or cake; (b) mixing, in one or more mixing steps, the at least solid elastomer, the wetting filler, and the crosslinker to form a mixture and removing at least a portion of the liquid from the mixture by evaporation; and (c) discharging from the mixer the composite including the filler dispersed in the elastomer at a loading of at least 20 phr, wherein the composite has a liquid content of 10% by weight or less, based on the total weight of the composite. wherein the crosslinking agent is selected from compounds having at least two functional groups; The first functional group is —N(R 1 ) (R 2 ), -N(R 1 ) (R 2 ) (R 3 ) + A - , -S-SO 3 M 1 and structures represented by formula (I) and formula (II): 【Chemistry 1】 In the formula, A - is chloride, bromide, iodide, hydroxyl, nitrate or acetate, X=NH, O or S, Y=H, OR 4 , N.R. 4 R 5 , -S n R 4 and n is an integer selected from 1 to 6; and The second functional group is a thiocarbonyl, a nitrile oxide, a nitrone, a nitrile imine, -S-SO 3 M 2 , -S x -R 6 , -SH, -C(R 6 ) = C(R 7 )-C(O)R 8 , -C(R 6 ) = C(R 7 )-CO 2 R 8 , -C(R 6 ) = C(R 7 )-CO 2 M 2 and R 1 ~R 8 are each independently H and C 1 ~C 8 alkyl, and M 1 and M. 2 are each independently H, Na + , K + , Li + , N(R′) 4 + where each R' is independently selected from H and C 1 ~C 20 alkyl, and x is an integer selected from 1 to 8; A method for preparing a composite material comprising:
2. The crosslinker further comprises at least one spacer between the first and second functional groups, the at least one spacer being -(CH 2 ) n -, -(CH 2 ) y C(O)-, -C(R 9 ) = C(R 10 )-, -C(O)-, -N(R 9 ) - and -C 6 H 4 -, where R 9 and R 10 are each independently H and C 1 ~C 8 2. The method of claim 1, wherein y is selected from alkyl, and y is an integer selected from 1 to 10.
3. The crosslinking agent is selected from the group consisting of thiourea, cystamine, and compounds of formula (1), formula (2), and formula (3), 【Chemistry 2】 The method of claim 1 , wherein the compound is selected from the group consisting of
4. M 1 and M. 2 are independently H, Na + and N(R′) 4 + and R 6 and R 7 independently H and C 1 ~C 6 The method of any one of claims 1 to 3, wherein the alkyl group is selected from alkyl.
5. The crosslinking agent is selected from compounds of formula (1) and R 6 and R 7 The method of claim 4 , wherein each is H.
6. The method of any one of claims 1 to 5, wherein the cross-linking agent is sodium (2Z)-4-[(4-aminophenyl)amino]-4-oxo-2-butenoate.
7. The method of any one of claims 1 to 6, wherein the step of charging comprises separately charging the crosslinker and the wetting filler into the mixer.
8. The method of any one of claims 1 to 7, wherein the filling step comprises multiple additions of the solid elastomer, the wetting filler, and / or the crosslinker.
9. 9. The method according to any one of claims 1 to 8, wherein in at least one of said mixing steps, said method comprises carrying out said mixing step in which said mixer has at least one temperature control means set at a temperature, Tz, of 65°C or higher.
10. 10. The method of any one of claims 1 to 9, wherein in at least one of the mixing steps, the method comprises carrying out the mixing step with one or more rotors of the mixer operating at a tip speed of at least 0.6 m / sec for at least 50% of the mixing time.
11. 11. The method of any one of claims 1 to 10, wherein the wet filler further comprises at least one material selected from carbonaceous materials, silica, nanocellulose, lignin, clay, nanoclay, metal oxides, metal carbonates, pyrolytic carbon, graphene, graphene oxide, reduced graphene oxide, carbon nanotubes, single-walled carbon nanotubes, multi-walled carbon nanotubes, or combinations thereof, and coated and treated materials thereof.
12. The method of any one of claims 1 to 10, wherein the wetting filler further comprises silica.
13. A method according to any one of the preceding claims, wherein the wetting filler has liquid present in an amount in the range of 20% to 80% by weight, based on the total weight of the wetting filler.
14. 14. The method according to any one of claims 1 to 13, wherein the solid elastomer is selected from natural rubber, functionalized natural rubber, styrene-butadiene rubber, functionalized styrene-butadiene rubber, polybutadiene rubber, functionalized polybutadiene rubber, polyisoprene rubber, ethylene-propylene rubber, isobutylene based elastomers, polychloroprene rubber, nitrile rubber, hydrogenated nitrile rubber, polysulfide rubber, polyacrylate elastomers, fluoroelastomers, perfluoroelastomers, silicone elastomers, and mixtures thereof.
15. 14. The method of any one of claims 1 to 13, wherein the solid elastomer is selected from natural rubber, functionalized natural rubber, styrene-butadiene rubber, functionalized styrene-butadiene rubber, polybutadiene rubber, functionalized polybutadiene rubber, and mixtures thereof.
16. 16. A method for preparing a vulcanizate, comprising curing the composite prepared by the method of any one of claims 1 to 15, in the presence of at least one curing agent to form the vulcanizate.
Citation Information
Patent Citations
Method for manufacturing tire
JP2018062154A
Method for manufacturing tire member
JP2018062613A
Method for producing silica and carbon black reinforced elastomeric composites and products containing same
JP2018524450A
Method for producing silica reinforced elastomeric composites and products containing same
JP2018528283A
Method of producing master batch, method of producing rubber composition for tire, and method of manufacturing tire
JP2019089901A